Porous carbon material, method for producing same, and electric storage device using same
By using graphene skeleton porous carbon material with a particle size of 300 nm or more and 30 μm or less, and using a specific manufacturing method, the problem of insufficient carbon amount caused by nanoparticle aggregation is solved, and the effect of improving the performance of the power storage device is achieved.
Patent Information
- Application Number
- CN202380055050.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-25
- Publication Date
- 2025-03-07
AI Technical Summary
Existing porous carbon materials are prone to nanoparticles agglomeration during the manufacturing process, resulting in insufficient carbon content in the pores and affecting device performance.
A porous carbon material having a graphene skeleton is used, and the primary particles have a particle size of 300 nm or more and 30 μm or less. The carbon layer is fully coated and separated by a specific manufacturing method, including a coating process and a separation process.
The performance of electrical storage devices is achieved, such as the rate characteristics and output characteristics of capacitors and lithium-ion rechargeable batteries, and the reduction of device performance is avoided.
Smart Images

Figure CN119585201A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a porous carbon material and a method for producing the same, as well as a power storage device using the same. More specifically, the present invention relates to a structure called a mesoporous carbon sponge (CMS: carbon mesosponge) or a graphene mesosponge (GMS: graphene mesosponge) and a method for producing the same, as well as a capacitor or a lithium-ion rechargeable battery using the same as an electrode active material or a conductive aid. Background Art
[0002] In recent years, efforts to realize a sustainable society have attracted much attention. In particular, research and development for carbon neutrality, which aims to reduce greenhouse gas emissions to zero, has been actively carried out, and research on new carbon materials for improving the performance of power storage devices such as rechargeable batteries and electric double-layer capacitors (EDLCs) is being promoted around the world.
[0003] Graphene is one of the new carbon materials, with excellent thermal conductivity, electrical conductivity, and mechanical (tensile) strength, and its application in various fields such as electronics and energy materials has been studied. As such a graphene structure, the research and development of graphene mesoporous sponge is also being promoted. From the size of its specific surface area and conductive properties, it is expected to be used in battery negative electrode active materials, EDLC electrode auxiliary materials and other power storage devices.
[0004] As a method for manufacturing a porous carbon material containing graphene, in particular a graphene mesoporous sponge, it is known that after coating the surface of mold particles with carbon, the mold particles are removed, and the carbon material is heat-treated at a high temperature to manufacture a graphene mesoporous sponge (Patent Documents 1 and 2). As a method for coating the surface of a mold with carbon, a chemical vapor deposition (CVD: Chemical Vapor Deposition) method is known. In Patent Documents 1 and 2, methane is disclosed as a raw material gas in the CVD method, and as mold particles, aluminum oxide nanoparticles are specifically disclosed in Patent Document 1, and magnesium oxide nanoparticles are specifically disclosed in Patent Document 2. Prior art literature Patent Literature
[0005] Patent Document 1: Japanese Patent No. 6460448 Patent Document 2: Japanese Patent Application Publication No. 2021-84819 Summary of the invention Problems to be solved by the invention
[0006] Here, the terms used in this specification are explained for mold particles. Regarding nanoparticles such as aluminum oxide and magnesium oxide, for example, the case where they are formed by a bottom-up liquid phase method is exemplified. Here, a substance in which uniform nanoparticles are formed in a liquid, and then a structure formed by unevenly agglomerating the nanoparticles in the liquid is dried to form a powder is called a nanoparticle, and a substance in which a structure formed by unevenly agglomerating the nanoparticles in a liquid is dried to form a powder is called a porous body. In addition, the structure of the smallest unit of the powder constituting the porous body is called the primary particle of the porous body. For example, particles in which the powder of the porous body is dispersed by ultrasound or a homogenizer and observed by SEM or the like are equivalent to the primary particles of the porous body.
[0007] Generally, nanoparticles are easily directly aggregated, and the powder materials used in Patent Documents 1 and 2 are also easily powders having a structure in which secondary particles formed by aggregation of nanoparticles are the smallest unit when observed by SEM or the like.
[0008] The carbon material of Patent Document 1 is coated with carbon using secondary particles formed by agglomeration of aluminum oxide nanoparticles as a casting mold, and then the aluminum oxide secondary particles used as a casting mold are dissolved, and the residue is subjected to high-temperature heat treatment, thereby forming GMS. The carbon material of Patent Document 2 is coated with carbon using secondary particles formed by agglomeration of magnesium oxide nanoparticles as a casting mold, and then the magnesium oxide secondary particles used as a casting mold are dissolved, and the residue is subjected to high-temperature heat treatment, thereby forming GMS. In Patent Documents 1 and 2, by such a formation method, a high specific surface area corresponding to the specific surface area of the secondary particles used as a casting mold can be achieved.
[0009] However, in the porous carbon materials of Patent Documents 1 and 2, the nanoparticles as the mold are easily aggregated, and it is difficult to coat the pores in the aggregate with carbon, and there is a problem that the amount of carbon in the pores of the porous carbon material after removing the mold is insufficient. In addition, when such porous carbon materials are used in devices, there are problems such as reduced device performance.
[0010] In the case of EDLC as an example of a device, due to the fact that the amount of carbon formed in the pores in the aggregate is insufficient, the conductive path is limited, the diffusion resistance increases, and the electrostatic capacitance and charging rate decrease.
[0011] In addition, if we take lithium-ion rechargeable batteries as an example, especially when used for electric vehicles (EVs), the amount of conductive material is increased to reduce electrode resistance in order to improve output characteristics. As a result, the amount of active material that is the source of capacitance is reduced, making it impossible to achieve both high output and high capacitance.
[0012] The present invention has been accomplished in view of the above circumstances, and its object is to provide a porous carbon material and a method for producing the same without reducing device performance, as well as a capacitor and a lithium ion rechargeable battery using the porous carbon material as an electrode active material or a conductive aid. Means for solving problems
[0013] The inventors of the present invention have repeatedly conducted in-depth research and found that, compared with carbon materials such as those in Patent Documents 1 and 2, porous carbon materials having a graphene skeleton and a plurality of pores inside primary particles constituting the porous carbon material, and a primary particle size of 300 nm to 30 μm, have more conductive pathways, and when used as a power storage device, the diffusion resistance is reduced, thereby realizing a power storage device with high rate characteristics, such as a capacitor or a lithium-ion rechargeable battery.
[0014] That is, the present invention provides the following structure. (1) A porous carbon material having a graphene skeleton, wherein a plurality of pores are provided inside primary particles constituting the porous carbon material, and the particle diameter of the primary particles is 300 nm or more and 30 μm or less.
[0015] (2) The porous carbon material according to (1) above, wherein the primary particles are in a plate-like shape with (in-plane length)×(thickness) of 100 nm to 30 μm×10 to 1000 nm.
[0016] (3) A porous carbon material according to (1) or (2) above, wherein the primary particle is in a plate-like shape, and the porous carbon material has: a first wall portion, which mainly constitutes a surface (main surface) extending in a plate-like shape; and a second wall portion, which is constituted within the primary particle and constitutes a part of the partition wall inside the particle.
[0017] (4) The porous carbon material according to any one of (1) to (3) above, wherein a diffusion resistance of a capacitor obtained using the porous carbon material is 20Ω or less.
[0018] (5) The porous carbon material according to any one of (1) to (4) above, wherein a pore diameter of the porous carbon material is 2 nm or more and 50 nm or less.
[0019] (6) A method for manufacturing a porous carbon material, comprising: a coating step, in which a carbon layer is coated on a porous casting mold having a primary particle size of not less than 300 nm and not more than 30 μm to obtain a molded product; and a separation step, in which the porous casting mold is dissolved with an acid to separate the molded product from the porous casting mold.
[0020] (7) The method for producing a porous carbon material according to (6) above, further comprising a heat treatment step of heat-treating the porous mold before the coating step.
[0021] (8) The method for producing a porous carbon material according to (6) or (7) above, wherein the porous mold is composed of particles containing an oxide of an alkaline earth metal.
[0022] (9) The method for producing a porous carbon material according to any one of (6) to (8) above, wherein the oxide of the alkaline earth metal is magnesium oxide.
[0023] (10) The method for producing a porous carbon material according to any one of (6) to (9) above, wherein in the separation step, the porous mold is dissolved with an acid that does not contain hydrofluoric acid.
[0024] (11) A method for producing a porous carbon material according to any one of (6) to (10) above, further comprising, after the separation step, a stabilization step of heat-treating the molded product separated from the porous casting mold by the separation step.
[0025] (12) The method for producing a porous carbon material according to any one of (6) to (11) above, wherein the average skeleton thickness of the porous mold is 70 nm or less.
[0026] (13) A capacitor electrode comprising an electrode using the porous carbon material described in (1).
[0027] (14) A negative electrode for an electricity storage device, comprising the porous carbon material described in (1) as a conductive auxiliary agent.
[0028] (15) A positive electrode for an electricity storage device, comprising the porous carbon material described in (1) as a conductive auxiliary agent.
[0029] A power storage device comprising a positive electrode and / or a negative electrode containing the porous carbon material described in (1) as a conductive auxiliary agent. Effects of the Invention
[0030] According to the present invention, by using a porous casting mold with an appropriate primary particle size, a porous carbon material with little agglomeration effect and a method for manufacturing the same can be provided. By using the porous carbon material, a capacitor as a power storage device with improved device performance, such as rate characteristics, and a high-output power storage device having a positive electrode and / or a negative electrode containing the porous carbon material as a conductive additive can be realized. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1A This is a schematic perspective view showing an example of the structure of a porous carbon material according to one embodiment of the present invention. Figure 1B It is along Figure 1A A schematic cross-sectional view taken along line AA in FIG. Figure 2A Yes means Figure 1A A schematic three-dimensional diagram of an example of a structure in which multiple porous carbon materials are stacked. Figure 2B It is along Figure 2A A schematic cross-sectional view taken along line AA in FIG. Figure 3 This is an equivalent circuit model when measuring the diffusion resistance of a capacitor obtained by using the porous carbon material of FIG. 1 and FIG. 2 . Figure 4A This is a schematic perspective view showing an example of the structure of a porous casting mold used in a method for producing a porous material according to an embodiment of the present invention. Figure 4B It is along Figure 4A A schematic cross-sectional view taken along line BB in FIG. Figure 5A This is a diagram for explaining a method for producing a porous material according to one embodiment of the present invention, and is a schematic perspective view showing an example of the structure of a formed product obtained through a coating step. Figure 5B It is along Figure 5A Schematic cross-sectional view taken along line CC in FIG. Fig. 6A It is a diagram for explaining a method for producing a porous material according to one embodiment of the present invention, and is a diagram showing a state of a separation step. Figure 6B It is along Fig. 6A Schematic cross-sectional view taken along line CC in FIG. Fig. 7A This is a schematic perspective view showing an example of the structure of a porous material according to a modification of FIG. 1 . Figure 7B It is along Fig. 7A A schematic cross-sectional view taken along line EE in FIG. Figure 8 This is an electron microscope image of the porous mold used in Example 1. Fig.9A This is a SEM image of the porous mold of Production Example 2 at a magnification of 30,000. Fig. 9B This is a SEM image of the porous mold of Production Example 2 at a magnification of 100,000 times. Fig. 10A This is a SEM image of the molded product of Production Example 3 at a magnification of 30,000 times. Fig. 10B This is a SEM image of the molded product of Production Example 3 at a magnification of 100,000 times. Fig.11A This is a SEM image of the porous carbon material of Example 1 at a magnification of 30,000 times. Fig. 11B This is a SEM image of the porous carbon material of Example 1 at a magnification of 100,000 times. Fig. 12A This is a SEM image of the porous carbon material of Example 2 at a magnification of 30,000 times. Fig. 12B This is a SEM image of the porous carbon material of Example 2 at a magnification of 100,000 times. Fig.13 This is a SEM image of the carbon material of Comparative Example 1. Fig.14A This is a TEM image of the porous casting mold of Production Example 2. Fig. 14B This is a TEM image of the porous casting mold of Production Example 2. Fig.15A This is a TEM image of a molded product in Production Example 3 in which a carbon layer is coated on a porous mold. Fig. 15B This is a TEM image of a molded product in Production Example 3 in which a carbon layer is coated on a porous mold. Fig.16A is a TEM image of the porous carbon material of Example 1. Fig. 16B is a TEM image of the porous carbon material of Example 1. Fig.17A This is a TEM image of the porous carbon material of Example 2. Fig. 17B This is a TEM image of the porous carbon material of Example 2. Fig.18 The particle size distributions of the porous carbon materials of Examples 1, 2 and 2-B, the porous molds of Production Examples 1 and 2, and the molded products of Production Example 3 are shown. Fig.19 It is the particle size distribution of the porous carbon materials of Example 2 and Example 2-B and the carbon materials of Comparative Examples 1, 2 and 3. Fig. 20A These are the XRD analysis results of Production Examples 1 and 2. Fig. 20B Yes Fig. 20A The analysis results of Production Examples 1 and 2 are shown in a graph overlapped with each other so that the magnitudes of the vertical axes are aligned, and the peak of magnesium hydroxide is also shown. Fig.21 It is the XRD analysis result of Example 1 and Example 2. Fig. 22 It is the Raman spectra of Example 1, Example 2 and HOPG. Fig.231 and 2 are the nitrogen adsorption-desorption isotherms of the porous carbon materials of Example 1 and Example 2. Fig.24 These are nitrogen adsorption-desorption isotherms of the porous molds of Production Examples 1 and 2 and the molded product of Production Example 3. Fig.25 The pore size distributions of the porous molds of Production Examples 1 and 2 and the molded product of Production Example 3 are shown. Fig.26 1 and 2 are the pore size distributions of the porous carbon materials of Examples 1 and 2. Fig. 27 This is the TG curve of the porous casting mold of Production Example 1. Fig.28 This is the TG curve of the molded product of Production Example 3. Fig.29 TG curves of the porous carbon materials of Example 1 and Example 2. Fig.30 This is a diagram showing the TG curve of the porous carbon material of Example 2 together with the TG curves of other carbon materials. Fig.31 This is a diagram for explaining the ultra-high sensitivity vacuum TPD device used in Examples 1 and 2. Fig.32A This is the gas discharge pattern when temperature rising desorption analysis was performed on Example 1. Fig.32B This is the gas discharge pattern when temperature desorption analysis was performed on Example 2. Fig.33A This is an equivalent circuit model for calculating the diffusion resistance in Example 4-1 and Comparative Example 4-1. Fig.33B This is the Nyquist diagram of Example 4-1. Fig.33C This is the Nyquist plot of Comparative Example 4-1. Fig.34 It is a graph showing the rate characteristics of Example 4-1 and Comparative Example 4-1. Fig.35A This is an equivalent circuit model for calculating the diffusion resistance in Example 4-2 and Comparative Example 4-2. Fig.35B This is the Nyquist diagram of Example 4-2. Fig.35C This is the Nyquist plot of Comparative Example 4-2. Fig.36 It is a schematic cross-sectional view of an electric storage device (lithium ion secondary battery) according to one embodiment of the present invention. Fig.37 This is a diagram showing a discharge curve showing a current difference during discharge of the power storage device (lithium ion secondary battery) according to one embodiment of the present invention. DETAILED DESCRIPTION
[0032] Hereinafter, an example of an embodiment of the present invention will be described. The present invention is not limited to the following examples. The accompanying drawings used in the following description are schematic diagrams of partially enlarged representations of features in order to facilitate understanding of the features of the present invention. Therefore, the number of components, dimensional ratios, etc. are sometimes different from the actual ones. The materials, dimensions, quantities, etc. illustrated in the following description are examples, and the present invention is not limited to these, and can be implemented by appropriately changing within the scope of not changing its purpose.
[0033] [Graphene mesoporous sponge] Figure 1A and Figure 1B is a perspective view showing an example of the structure of a porous carbon material according to one embodiment of the present invention ( Figure 1A ) and a cross-sectional view taken along line AA in the stereogram ( Figure 1B ). Figure 2A and Figure 2B Yes means Figure 1A A three-dimensional diagram of an example of a structure in which a plurality of porous carbon materials are stacked ( Figure 2A ) and a cross-sectional view taken along line AA in the stereogram ( Figure 2B ). The porous carbon material of this embodiment includes a mesoporous carbon sponge (CMS) and a graphene mesoporous sponge (GMS) obtained from the CMS. Figure 1A and Figure 1B as well as Figure 2A and Figure 2B In FIG. 1 , GMS is shown as an example. Figure 1A and Figure 1B as well as Figure 2A and Figure 2B The GMS 100A shown is a porous carbon material having a graphene skeleton. A plurality of pores P are provided inside a primary particle 10A constituting the GMS 100A. The particle diameter of the primary particle 10A is 300 nm or more and 30 μm or less. Figure 1A and Figure 1B , Figure 2A and Figure 2B represents GMS as an example of a porous carbon material, and Figure 1A and Figure 1B , Figure 2A and Figure 2B The dot pattern in represents a state stabilized by heat treatment of CMS. The details of heat treatment of CMS will be described later.
[0034] The basic skeleton of GMS100A is graphene. GMS100A has, for example, one or more layers of graphene skeleton. In GMS100A, the average number of graphene stacking layers N is, for example, 0.9 to 5.0, preferably 1.0 to 2.0. The fewer the graphene stacking layers, the larger the specific surface area of the porous carbon material.
[0035] The average number of graphene layers N in GMS100A can be calculated by the following formula (1) based on the results of TG measurement. In formula (1), W carbon (g / g) represents the carbon loading amount calculated from the weight at the reference temperature and the weight after the carbon material is burned, S template (m 2 / g) represents the specific surface area of the mold, W M (g / m 2 ) represents the amount of carbon deposited per unit area of the mold, W graphene Indicates the weight per unit area of graphene. W carbon (g / g) and S template (m 2 / g) was calculated by TG measurement.
[0036] [Number 1]
[0037] The specific surface area of GMS100A is, for example, 800 to 2300 m 2 / g, preferably 1500 to 2300 m 2 / g, more preferably 1800 to 2300 m 2 / g. By increasing the specific surface area, the yield rate of the weight of the GMS relative to the weight of the mold becomes higher. In addition, the specific surface area of GMS100A is large, thereby increasing the capacitance as an electric storage device. The specific surface area of GMS100A is calculated by the BET method in accordance with JISZ8830:2013.
[0038] The pore diameter da of the pores P provided inside the primary particles of GMS100A is, for example, 1 nm to 50 nm, or 2 nm to 50 nm, or 1.5 nm to 30 nm, or 2 nm to 10 nm. Thus, GMS100A has a mesoporous structure having mesopores.
[0039] The pore diameter da of the pores P is calculated by the BJH method in accordance with JIS Z8831-2:2010.
[0040] As described above, the particle size (primary particle size) of the primary particle 10A of GMS100A is greater than 300nm and less than 30μm, and can be greater than 300nm and less than 20μm, or greater than 300nm and less than 10μm. The primary particle size of GMS100A is measured by SEM images observed with a scanning electron microscope. Specifically, GMS100A is observed in a range of 5000 times to 50,000 times by scanning electron microscope images when it is dispersed by ultrasonic treatment for 30 minutes using a 30 ultrasonic disperser or when it is dispersed by treatment for 10 minutes using a homogenizer, and the average of the maximum diameters of 100 randomly selected GMS100A primary particles 10A (wherein, the same observation image may also include multiple primary particles that are the objects of observation) is taken as the primary particle size of GMS100A. The particle size distribution of GMS100A measured by laser diffraction method or the like is 300 nm to 30 μm, but may be 300 nm to 20 μm, 500 nm to 10 μm, or 1 μm to 20 μm.
[0041] In addition, when GMS100A is a plate-like particle, the in-plane length of the main surface of the primary particle 10A includes the major diameter in the long side direction (meaning the maximum diameter of the primary particle, and therefore synonymous with the primary particle diameter) and the maximum diameter in the short side direction orthogonal to the long side direction, i.e., the minor diameter, which is calculated by the same method as the method for calculating the primary particle diameter described above. Regarding the in-plane length of the primary particle 10A of GMS100A, in the SEM image observed with a scanning electron microscope, the primary particles with a maximum diameter of 300 nm or more are measured. The major diameter of the primary particle 10A of GMS100A is, for example, 300 nm to 100 μm, and can be 500 nm to 50 μm. The minor diameter of the primary particle 10A is, for example, 100 nm to 30 μm, and can be 300 nm to 10 μm. The thickness of the primary particle 10A is 10 nm to 15 μm, and can be 30 nm to 1 μm. In the SEM image observed by scanning electron microscope, select particles with any diameter greater than 300 nm (not limited to the maximum diameter of the particle) whose length values of all parts orthogonal to the selected diameter are less than 1 / 3 of the selected diameter, measure the minimum value of the length orthogonal to the selected diameter, obtain the average of the measured values related to 100 randomly selected primary particles, and thus calculate the thickness of the primary particle 10A.
[0042] GMS100A is composed of, for example, one or more porous particles having a porous core-shell structure derived from a porous mold described below. The porous core-shell structure corresponds to the shape of the porous mold, for example, a shape reflecting the surface shape of the porous mold.
[0043] In GMS100A, for example, the primary particles 10A are plate-like in shape. Figure 1A and Figure 2A In the figure, the outer contour of GMS10A is indicated by a double-dashed line, but is not limited thereto. GMS10A has, for example: a first wall portion 11, which mainly constitutes the plate-shaped main surface S; and a second wall portion 12, which is formed in the primary particle 10A and constitutes a part of the partition wall inside the particle. Figure 1B and Figure 2B In the figure, as a schematic diagram, the main surface of GMS10A is represented by a double dotted line, but it is not limited to this. In addition, the first wall portion 11 may also constitute a part of the plate-like main surface S. It should be noted that the situation in which the primary particle 10A is in a plate-like shape can be confirmed by the ratio of the diameter selected above to the thickness of the primary particle diameter calculated above being 3 times or more. From the viewpoint of diffusion resistance, the ratio of the diameter selected above to the thickness of the primary particle diameter is preferably 5 times or more, and more preferably 10 times or more.
[0044] The first wall portion 11 is a portion of the GMS 10A constituting the main surface S, such as the topmost or bottommost portion. The second wall portion 12 is a portion located in the primary particle between the two main surfaces S of the GMS 10A. The second wall portion 12 includes, for example, a wall extending upward in a direction along the main surface S and a wall extending upward in a direction intersecting the main surface S, and the interior of the GMS 100A is finely divided by these walls. A plurality of pores P defined by the first wall portion 11 and the second wall portion 12 or a plurality of second wall portions 12 are provided in the primary particle 10A of the GMS 100A.
[0045] EDLC is exemplified as an example of a device to which the GMS100A of the present embodiment is applied. The diffusion resistance of a capacitor of the EDLC produced using the EDLC is 22Ω or less, preferably 20Ω or less, and more preferably 18Ω or less.
[0046] Here, the diffusion resistance is the diffusion resistance measured between two electrodes of a capacitor obtained by using a paste which is a mixture of GMS100A, a conductive auxiliary agent and a binder. The mixing ratio of GMS (graphene mesoporous sponge), a conductive auxiliary agent and a binder in the mixture used to form the above capacitor is 70-95:20-0:30-1.
[0047] The following describes the assembly of a bipolar battery for obtaining the above-mentioned diffusion resistor. First, a paste is prepared by mixing a quantitative amount of GMS, a conductive aid, and a binder in the above-mentioned mixing ratio, and preparing two molded bodies weighing 5 mg and measuring 1 cm x 1 cm. Next, the molded body is clamped with a Pt mesh and pressed with a manual press at a displayed pressure of about 3 KN to form an electrode. Two of these electrodes are prepared in such a way that they have the same weight in terms of weight ratio, and they are used as the positive electrode and the negative electrode, respectively. After drying the prepared electrodes at 120°C under vacuum overnight, the button batteries are assembled in a glove box under an argon atmosphere.
[0048] The assembly of button batteries is to stack and accommodate the spring, spacer, electrolyte, negative electrode, diaphragm (glass fiber), electrolyte, positive electrode, electrolyte and spacer in the stacking direction between the outer body. The assembly of button batteries is to gently tighten the electrodes and diaphragms, and then crimp them using a special assembly tool (made by Hosen, model: HSMCC-H10). As the electrolyte, 1M Et4NBF4 / PC (PC = propylene carbonate) can be used.
[0049] For the button cells made in this way, electrochemical measurements were performed using a potentiostat (Bio-Logic: VMP3). Specifically, after standing in a constant temperature box maintained at 25°C for 24 hours, impedance measurements were performed before cyclic voltammetry and constant current charge and discharge measurements. The obtained data were fitted using the analysis software ZView2 to estimate the diffusion resistance. Figure 3 The equivalent circuit model is shown. Figure 3 This is an equivalent circuit model for measuring the diffusion resistance of a capacitor obtained using the porous carbon material of Figures 1 and 2. Figure 3 In the figure, R1 represents the solution resistance, R2 represents the charge transfer resistance, CPE1 represents the interface capacitance, and W1 represents the diffusion resistance.
[0050] The total pore volume of GMS100A is, for example, 0.5 to 6.0 cm 3 / g, preferably 1.0 to 5.0 cm 3 / g, more preferably 1.2 to 4.0 cm 3 The total pore volume of GMS100A was calculated by converting the nitrogen adsorption amount at a relative pressure of P / P0=0.96 at -196°C into a volume at the density of liquid nitrogen to obtain an adsorption-desorption isotherm.
[0051] [Method for producing porous carbon material] The method for manufacturing the porous carbon material of the present embodiment comprises a coating step of coating a porous casting mold having a primary particle size of not less than 300 nm and not more than 30 μm with a carbon layer to obtain a molded product, and a separation step of dissolving the porous casting mold with an acid to separate the molded product from the porous casting mold. In addition, the method for manufacturing the graphene mesoporous sponge body further comprises a stabilization step of heat-treating the molded product separated from the porous casting mold by the separation step after the separation step. Preferably, the method for manufacturing the graphene mesoporous sponge body of the present embodiment further comprises a heat treatment step of heat-treating the porous casting mold before the coating step. Hereinafter, appropriate references are made to Figures 4A to 7B , the method for producing the porous carbon material of this embodiment is described. Figures 4A to 7B In, with Figure 1A as well as Figure 1B The same components are denoted by the same reference numerals, and description thereof will be omitted.
[0052] (Heat treatment process) First, the porous mold is heat treated. Figure 4A is a schematic perspective view showing an example of the structure of a porous casting mold used in a method for producing a porous material according to an embodiment of the present invention, Figure 4B This is a schematic cross-sectional view taken along line BB in the perspective view. Figure 4A and Figure 4B The state of the porous mold 20 before the coating step to be performed later is shown. Figure 4A and Figure 4B The porous mold 20 shown is a primary particle of the mold material, and has a three-dimensional skeleton P' inside. The primary particle size of the porous mold 20 is 300 nm or more and 30 μm or less. The primary particle size of the porous mold 20 can be observed by observing the major axis, minor axis, and thickness in the same way as the primary particle size of GMS100A. In addition, the primary particles of the porous casting mold are composed of a porous body.
[0053] The heat treatment of the porous mold is carried out, for example, in an inert gas atmosphere, an air atmosphere, or a vacuum. The heat treatment of the porous mold is, for example, heated at 400 to 1100°C, preferably at 500 to 1000°C, and more preferably at 600 to 950°C. The heat treatment of the porous mold is, for example, carried out for 0.1 to 3 hours, preferably for 0.2 to 1 hour. Before the coating process, by heat treating the porous mold under the above-mentioned conditions, the impurities can be decomposed when impurities are mixed in the porous mold. As a specific example, when using a porous mold composed of magnesium oxide, the magnesium hydroxide and magnesium carbonate mixed in the mold are decomposed and separated from the mold by heat treatment. Through the above-mentioned heat treatment process, the specific surface area S of the porous mold can be increased, and the pore diameter db can be increased.
[0054] Figure 4A and Figure 4B The porous casting mold 20 shown is a casting mold having a porous structure made of any material. From the viewpoint of avoiding the use of hydrofluoric acid in the separation process, it is preferably made of an oxide of an alkaline earth metal, and more preferably made of magnesium oxide (MgO), calcium carbonate, and calcium oxide. It should be noted that when hydrofluoric acid is used in the separation process, a porous casting mold 20 made of aluminum oxide, zeolite, etc. can be used. A plurality of gaps G defined by a skeleton portion P' are provided inside the porous casting mold 20, for example.
[0055] The average skeleton thickness d of the porous mold 20 is, for example, 5 to 70 nm, preferably 7 to 40 nm, and more preferably 10 to 30 nm. The larger the average skeleton thickness d, the more flexible the carbon skeleton is.
[0056] The average skeleton thickness d of the porous mold 20 is obtained by the following formula (2). The average skeleton thickness d is the equivalent spherical diameter of the skeleton of the porous mold 20. That is, the diameter d when assuming a sphere with the same specific surface area as the unit skeleton of the porous mold 20 is obtained by formula (2). Here, the specific surface area (BET specific surface area) of the porous mold 20 in the formula is calculated by the BET method based on JIS Z8830: 2013. d = 6.0 × 10 3 / (S×ρ)···(2) (where d represents the average skeleton thickness [nm], and ρ represents the density of the material constituting the porous mold [g / cm 3 ], S represents the BET specific surface area of the porous mold [m 2 / g]. )
[0057] (Coating process) Next, Figure 4A and Figure 4B The porous mold 20 shown is coated with a carbon layer 35 to obtain a molded product 30. Specifically, the surface of the porous mold 20 is coated with the carbon layer 35. Figure 5A is a diagram for explaining a method for producing a porous material according to an embodiment of the present invention, and is a schematic perspective view showing an example of the structure of a formed product obtained by a coating step. Figure 5B It is a schematic cross-sectional view taken along the CC line in the perspective view. Figure 5A and Figure 5B The molded product 30 shown is a porous mold 20 covered with a carbon layer 35 (black thick line). The carbon layer 35 is formed along the surface shape of the skeleton portion P′ of the porous mold 20.
[0058] The coating of the porous mold 20 with the carbon layer 35 can be performed by any of a wet method such as an impregnation method, a dry method such as a chemical vapor deposition method (CVD method), or a combination of the wet method and the dry method, where the dry method is performed after the wet method. From the viewpoint of controlling the number of stacked layers of the formed carbon layer 35 to 1 layer or more, the coating of the carbon layer 35 in the coating step is preferably performed by effectively utilizing a chemical vapor deposition method (CVD: Chemical Vapor Deposition) method which is a dry method.
[0059] Hereinafter, this embodiment will be described by taking as an example a method of obtaining a molded product 30 by coating a porous mold 20 with a carbon layer 35 by a CVD method. The coating with the carbon layer 35 by the CVD method may be performed in a plurality of steps.
[0060] In the coating process, as the raw material gas of the CVD method, acetylene, methylacetylene, ethylene, propylene, isoprene, cyclopropane, methane, ethane, propane, benzene, toluene, vinyl compounds, ethylene oxide, methanol, ethanol, acetonitrile, acrylonitrile and the like are used. From the viewpoint of making it easy for the gas to enter the gap G of the porous mold 20, acetylene, ethylene, propylene, methane and ethane are preferably used as the raw material gas.
[0061] When the coating step is performed by CVD, heating is performed at a temperature of, for example, 400 to 1500° C., and a pressure of, for example, 1 to 200 kPa. The heating rate in the coating step is, for example, 1 to 50° C. / min.
[0062] In the coating process, in addition to the above-mentioned raw material gas, for example, an inert gas may be used as a carrier gas. In addition, as a carrier gas, in addition to the inert gas, a gas containing oxygen, hydrogen, etc. may be used. In the coating process, from the viewpoint of coating 1 to 2 layers of the carbon layer 35, it is preferred to control the flow rate of the carrier gas to 0.05 to 1.00 m / min, and the amount of the raw material gas to the total amount of the raw material gas and the carrier gas to 1 to 60 volume %.
[0063] In the coating step, when a wet method is performed, for example, an organic compound may be impregnated and carbonized.
[0064] In addition, after the coating process, the porous casting mold 20 coated with the carbon layer 35 on the surface in the coating process can be heat treated. The heat treatment temperature is, for example, a temperature higher than the heat treatment temperature in the coating process, such as 900 to 1400°C. The heat treatment is performed, for example, by a method using a high-frequency induction heating furnace or a spark plasma sintering (SPS) method. The heat treatment can be performed in either an atmospheric atmosphere or an inert gas atmosphere, preferably under reduced pressure. By performing this heat treatment, the carbonization of the carbon layer 35 can be promoted.
[0065] (Separation process) Next, the porous mold 20 is dissolved by acid or the like, and the molded product 30 is separated from the porous mold 20 . Fig. 6A and Figure 6B It is a diagram for explaining a method for producing a porous material according to one embodiment of the present invention, and is a diagram showing a state of a separation step. Fig. 7A 1 is a schematic perspective view showing an example of the structure of a porous material according to a modification of FIG. 1 disclosed in an embodiment described later, and is a porous carbon material obtained after a separation step. Figure 7B This is a schematic cross-sectional view taken along line EE in the perspective view.
[0066] In the separation process, for example, use inorganic acids such as hydrofluoric acid, hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, boric acid, etc., organic acids or their mixtures having carboxyl, hydroxyl, thiol group, enol structure etc. in the molecule. When using the casting mold consisting of alkaline earth metal as the porous casting mold 20, dissolve the porous casting mold with the acid that does not contain hydrofluoric acid. Consider the safety aspect, environmental load, cost aspect, it is hoped that hydrofluoric acid is not used. If the casting mold consisting of the alkaline earth metal that can dissolve by the acid other than hydrofluoric acid such as hydrofluoric acid, sulfuric acid is used, then it can be avoided to use.
[0067] In addition, fluorine-containing acids such as hydrofluoric acid usually form insoluble compounds with alkaline earth metals contained in alkaline earth metal oxides, so insoluble compounds are formed in aqueous media during the dissolution process of alkaline earth metal oxides. In contrast, by using an acid that does not contain fluorine, insoluble salts will not be formed, and compounds that are easily soluble in aqueous media can be formed. That is, according to the present embodiment, by using an acid that does not contain hydrofluoric acid, in the case of using alkaline earth metal oxides, particularly magnesium oxide or calcium oxide that constitute a porous mold furnace body as a mold, the porous mold can be easily dissolved. Here, dissolving refers to when the mold is contacted with the acid of the aqueous medium, and finally no insoluble compound remains in the aqueous medium, forming a transparent and uniform liquid without turbidity.
[0068] In the separation step, the amount of the acid used to separate the molded product 30 from the porous mold 20 is, for example, 1 time or more, preferably 1.2 times or more, relative to the porous mold in terms of stoichiometric ratio. In the separation step, the temperature at which the porous mold 20 is dissolved by the acid can be, for example, in the range of 5 to 100° C. In the separation step, for example, stirring or vibrating the acid mixed with the porous mold can be performed.
[0069] In the separation process, the porous carbon material separated from the porous casting mold 20 can be recovered by filtration, for example, and then dried by vacuum heating and drying. The recovery of the porous carbon material can be performed by, for example, suction filtration. The vacuum drying and heating for obtaining the porous carbon material can be performed, for example, at a temperature of 100 to 200° C. and under conditions of 1 to 10 hours. From the viewpoint of avoiding capillary shrinkage of the porous carbon material caused by vacuum drying and heating, it is preferred to replace it with a solvent with low surface tension such as acetone or alcohols after suction filtration. The porous carbon material obtained by this process is CMS, which will be described in detail later. In the case of manufacturing the GMS of the above-mentioned embodiment, the porous carbon material is used as a precursor, followed by a stabilization process. The degree of capillary shrinkage depends on the shape and size of the porous carbon material, but sometimes shrinks to about half.
[0070] The shape and size of the porous carbon material obtained after the separation process correspond to the shape and size of the porous mold 20. Specifically, the shape of GMS100A corresponds to the shape and size of the carbon layer 35 coated on the surface of the porous mold 20, and the shape of the carbon layer 35 is, for example, a shape that reflects the surface shape of the porous mold 20. In the separation process, capillary contraction occurs due to the acid used, so the size of the obtained porous carbon material becomes smaller than the carbon layer 35 coated on the surface of the porous mold 20.
[0071] (Stabilization process) Next, after the separation step, the molded product separated from the porous mold 20 in the separation step is heat treated. In the stabilization step, the heat treatment of the molded product can be performed at 900 to 2000° C. for 0.1 to 5 hours, for example. The heat treatment of the molded product in the stabilization step is preferably performed at 1600 to 1800° C. for 0.5 to 2 hours.
[0072] Through the stabilization process, Figure 1A and Figure 1BGMS100A shown. By heat treating the molded object consisting of the carbon layer separated from the porous mold 20, the carbon layer can be stabilized. Specifically, by the above-mentioned heat treatment, the graphene mesh size in the porous carbon material can be increased and the amount of edge sites can be reduced. In the case of applying a porous carbon material with a small amount of edge sites to an electrode of an electric double layer capacitor (EDLC), even if a high voltage is applied, the electrolyte is difficult to decompose, and a high voltage can be applied, thereby further improving the energy density and also improving the reliability.
[0073] According to the method for manufacturing the porous carbon material of the present embodiment, a coating process of obtaining a molded product by coating a carbon layer on a porous mold having a primary particle size of 300 nm or more and 30 μm or less, and a separation process of separating the molded product from the porous mold by dissolving the porous mold with an acid, a porous carbon material having a primary particle size of 300 nm or more and 30 μm or less can be generated. In addition, according to the porous carbon material of the present embodiment, a porous carbon material having a graphene skeleton is provided inside the primary particle, and a plurality of pores are provided inside the primary particle constituting the porous carbon material, and the particle size of the primary particle is 300 nm or more and 30 μm or less, thereby reducing the diffusion resistance and improving the rate characteristics when effectively used as a power storage device. That is, according to the present embodiment, by using the porous carbon material of the present embodiment, a device that maintains a high energy density and improves the rate characteristics can be realized. It is believed that one of the main reasons for the above-mentioned diffusion resistance is that the conductive path can be increased by the structure of the shape derived from the porous mold.
[0074] In addition, GMS100A has a plate-like primary particle shape, so the interaction between the primary particles is reduced and it is difficult to aggregate. In addition, even if it cannot withstand the external force in the in-plane direction and aggregates, it is easy to eliminate the aggregation by ultrasonic dispersion or the like.
[0075] The porous carbon material of the present invention is not limited to the GMS100A of the above-mentioned embodiment, and various modifications can be made within the scope of the gist of the claims. Fig. 7A as well as Figure 7B CMS100B as shown. Fig. 7A Yes means Figure 1A and Figure 1B A schematic perspective view of an example of the structure of a porous material according to a modification of Figure 7B is a schematic cross-sectional view cut along the EE line in the stereogram. Fig. 7A and Figure 7B The porous carbon material shown is called CMS (mesoporous carbon sponge). The mesh surface (basal surface) size of CMS is smaller than that of GMS, for example, about 10 nm.
[0076] The pore diameter da of CMS100B is, for example, smaller than the average skeleton thickness d of the porous mold 20. The reason why the pore diameter da of the porous carbon material manufactured by the process of coating the surface of the porous mold 20 becomes smaller than the average skeleton thickness d of the porous mold 20 is mainly due to the above-mentioned capillary contraction generated when the porous carbon material is separated from the porous mold 20. The ratio da / d of the size of the pore diameter da of the porous carbon material to the size of the average skeleton thickness d of the porous mold is, for example, 0.1 to 1.0, and sometimes 0.1 to 0.8.
[0077] The particle size of the primary particles 10B of CMS100B is substantially the same as the particle size of the primary particles 10A of GMS100A. The specific surface area of CMS100B may be equal to or different from the specific surface area of GMS100A. For example, it is preferably 700 to 2400 (m 2 / g), more preferably 1700 to 2400 (m 2 / g).
[0078] The difference between the GMS100A involved in the above-mentioned embodiment and the CMS100B involved in the present embodiment can be made, for example, by X-ray diffraction (XRD) and Raman spectroscopy. Specifically, in XRD measurement, in GMS, the 10 peak near 2θ=43° and the 11 peak near 2θ=78° derived from the sheet structure of graphene are stronger than those in CMS. In addition, in Raman spectroscopy, in GMS, the intensity of the 2D band is higher than that in CMS.
[0079] Even in the case of CMS, a power storage device having high rate characteristics can be realized by providing a plurality of pores P inside primary particles 10B constituting CMS 100B as CMS 100B having a graphene skeleton and by setting the particle size of the primary particles 10B to 300 nm or more and 30 μm or less.
[0080] The porous carbon material of the above-described embodiment can be used in a variety of applications such as an adsorbent, a monomer of various catalysts, an electrode material for electric double layer capacitors and secondary batteries, and a conductive additive.
[0081] When removing the carbon material from the capacitor, a scraper is used to peel off the layer with a high carbon content facing the collector. This layer, for example, contains a carbon material, a conductive additive, and a binder. In order to remove the carbon material from this layer, first, it is washed with a solvent that is the same as the solvent used in the electrolyte to remove the electrolyte. In the presence of a solvent that can dissolve the binder used in electrode production, it is further washed with the solvent. Then, the solid content is recovered to determine that the carbon material contains the GMS of this embodiment.
[0082] Specifically, by observing the powder with TEM, it was determined that GMS and CMS have a characteristic mesoporous structure. Then, the powder was slowly heated to determine whether it contained GMS. In the thermogravimetric analysis under air circulation, it was confirmed in the embodiment that GMS was detached at about 700°C, and the detachment temperature among carbon materials was second only to HOPG. HOPG does not have a mesoporous structure. Therefore, by heating the powder containing the carbon material to 680°C, it can be determined that the carbon material that did not detach and remained was GMS.
[0083] The primary particles of GMS are obtained by mixing the residual carbon material with ethanol as an organic solvent and performing ultrasonic dispersion. The ultrasonic dispersion is performed for 30 minutes using an ultrasonic disperser and then for 30 minutes using a homogenizer. The primary particle size of GMS is determined by observing the dispersed powder with SEM, measuring the in-plane length of 100 primary particles in a 30,000-fold SEM image, and taking the average. In addition, the particle size distribution can be measured by a laser diffraction method, etc.
[0084] Next, a lithium ion secondary battery as the power storage device of the present invention will be described.
[0085] Fig.36 An example of the cross-sectional structure of an electric storage device 200 according to an embodiment of the present invention is shown as a coin-shaped lithium-ion battery. The lithium-ion battery is formed by stacking a disk-shaped positive electrode 212 contained in a metal outer casing 211 and a disk-shaped negative electrode 214 contained in a metal outer casing 213 via a separator 215. In addition, a metal spring 218 and a spacer 219 are arranged between the outer casing 213 and the negative electrode 214. The interior of the outer casing 211 and the outer casing 213 is filled with a liquid electrolyte, and the peripheral portions of the outer casing 211 and the outer casing 213 are sealed by riveting via a sealing gasket 217.
[0086] The positive electrode will be described. The positive electrode 212 is obtained, for example, as follows: a slurry containing a mixture of a metal oxide material, a conductive auxiliary material that assists electronic conductivity, a binder and a solvent is applied to a metal foil for current collection such as a rolled aluminum foil to form a coating, and then heated and dried to remove the solvent to form a predetermined size and density.
[0087] The metal compound material that can be used for the positive electrode active material refers to a material that can release Li ions into the electrolyte while releasing electrons into the external circuit of the battery. The amount of Li ions contained varies depending on its chemical composition, crystal structure, etc., and it is preferred that a material that can reversibly take out and put in a large amount of Li ions.
[0088] As the material, transition metal oxides, composite oxides of lithium and transition metals, transition metal sulfides, etc. are mentioned. As transition metals, Fe, Co, Ni, Mn, etc. are used. As specific examples, MnO, V2O5, V6O 13 Transition metal oxides such as TiO2, LiNiO2, LiCoO2, LiMn2O4, inorganic compounds such as TiS2, FeS, MoS2, etc., in order to improve their characteristics, substances in which specific elements are partially replaced by certain elements can also be used.
[0089] In addition to the above-mentioned inorganic compounds, there are also positive electrode materials composed of organic compounds. For example, polyaniline, polypyrrole, polyacene, disulfide compounds, polysulfide compounds, N-fluoropyridinium salts, etc. can be cited. The positive electrode material can be a mixture of the above-mentioned inorganic compounds and organic compounds.
[0090] The physical properties of the positive electrode material are determined by the requirements of the battery design and manufacturing process due to the constraints such as the utilization mode of the power storage device. In the manufacture of the positive electrode material, the process design is performed in a manner that can achieve its physical properties. Examples of physical property values include powder particle size and distribution, specific surface area, density, etc.
[0091] For example, the powder particle size can be appropriately selected in consideration of other constituent elements of the power storage device, and is usually preferably 1 to 30 μm, more preferably 1 to 10 μm, as an average value from the viewpoint of improving battery characteristics such as rate characteristics and cycle characteristics.
[0092] The positive electrode material generally has low electron conductivity, so it is preferred that a conductive aid for assisting electron conductivity coexists in the positive electrode. The conductive aid may be made of carbon-based materials, metal-based materials, or other materials with high electron conductivity, among which carbon-based materials are preferred.
[0093] The amount of the conductive auxiliary agent to be present is limited to the necessary minimum, and the content of the positive electrode material that specifies the capacity of the electricity storage device should be maximized.
[0094] Examples of conventional carbon-based materials include carbon black, acetylene black, Ketjen black, lamp black, furnace black, carbon black, graphite, carbon fiber, graphite fiber, nanofiber, nanotube, coke, hard carbon, and amorphous carbon.
[0095] Compared with these, the conductive aid of this embodiment has a major feature not found in conventional materials as described above, that is, the conductive aid of this embodiment has a fine structure like nanocarbon, elasticity against stress, and a high specific surface area and fewer oxygen-containing functional groups.
[0096] Due to this feature, the conductive additive can maintain the electronic conductivity of the electrode even in the electrochemical oxidation environment and stress environment to which the battery is exposed, thereby suppressing the degradation of the characteristics.
[0097] The preferred ratio of the conductive aid composed of the porous carbon material of this embodiment contained in the positive electrode varies depending on the type of positive electrode material, the type and amount of the binder, the battery capacitor design, etc., and is preferably 0.03wt% or more in the positive electrode mixture.
[0098] The positive electrode material and the conductive aid are mostly powdered, and in order to fix them to each other and to fix them on the current collecting metal foil, a small amount of binding material is preferably mixed and used. The binding material is required to be chemically and electrochemically inactive, have some flexibility and affinity, and preferably a plastic resin material is used.
[0099] Examples of the plastic resin material include fluorine resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene, CN-containing polymers such as polyacrylonitrile and polyvinylidene fluoride, polyvinyl alcohol polymers such as polyvinyl acetate and polyvinyl alcohol, halogen-containing polymers such as polyvinyl chloride and polyvinylidene chloride, conductive polymers such as polyaniline, alkane polymers such as polyethylene, polypropylene, and poly-1,1-dimethylethylene, unsaturated polymers such as polybutadiene and polyisoprene, polymers having a ring such as polystyrene, polymethylstyrene, polyvinylpyridine, and poly-N-vinylpyrrolidone, acrylic polymers such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polymethyl acrylate, polyethyl acrylate, polyacrylic acid, polymethacrylic acid, and polyacrylamide, etc. In addition, the above resin materials may be a mixture, a modified product, a derivative, a random copolymer, an alternating copolymer, a graft copolymer, a block copolymer, etc. The weight average molecular weight of these resins is usually 10,000 to 3,000,000, preferably 100,000 to 1,000,000. If the molecular weight is too small, the strength of the coating film decreases, and if it is too large, the viscosity increases, making it difficult to form an electrode.
[0100] In order to distribute the bonding material sufficiently and evenly and form the slurry coating into a predetermined size, a suitable slurry solvent that only dissolves the bonding material resin but does not dissolve other materials can be used. For example, in the case of using polyvinylidene fluoride, dimethylformamide is preferably used as the solvent. Alternatively, N-methylpyrrolidone can be used as the solvent, which can be appropriately selected and used according to the conditions of the manufacturing process.
[0101] The metal foil for current collection is preferably a material that can be obtained cheaply and can withstand industrial use, and preferably a material that has electrochemical resistance to the potential displayed by the positive electrode. As examples of the metal foil for current collection, aluminum foil, nickel foil, titanium foil, and stainless steel foil are preferred, and rolled aluminum foil that is generally easy to obtain is more preferred.
[0102] As a method for forming the coating film of the slurry, a commonly used printing technique can be used. When the thickness of the coating film is small, gravure printing or the like is suitable, and when the thickness is large, printing methods such as doctor blade printing and die printing are suitable.
[0103] Thereafter, the coating film is dried by heating. Any drying method may be used, but it is preferable to use a method that can achieve a desired adhesive strength with the adhesive material.
[0104] Then, when forming the positive electrode into a predetermined size, it is preferred to use an industrially available cutting blade and its method. In addition, in order to achieve a predetermined density, it is preferred to use an industrially available pressurizing device and its method as needed.
[0105] Next, the negative electrode will be described. The negative electrode 214 is obtained by, for example, applying a slurry made by mixing a carbon-based material, a binder and a solvent onto a current collecting metal foil such as a rolled copper foil, and heating and drying to remove the solvent to obtain a predetermined size and density.
[0106] As the carbon-based material that can be used for the negative electrode, a carbon-based material that can stabilize the bonding between Li ions and electrons flowing from an external circuit and has a plurality of stabilizing sites inside the carbon-based material is preferred.
[0107] As an example, any organic material can be used regardless of whether the crystallinity is high or low, and preferably graphite, coke, amorphous carbon, hard carbon, polymer carbon, etc. In this case, as a principle, Li ions are bonded to electrons and stabilized in the state of being sandwiched between graphene layers.
[0108] In addition, as another stabilizing mechanism, a method of electrochemically forming an intermetallic compound may be used, and silicon, tin, zinc, bismuth, antimony, cadmium, lead, germanium, etc. can be preferably used.
[0109] In addition, other materials that manage the negative electrode side of the power storage device and exhibit low electrochemical reaction potential may also be used, preferably compounds of metals and oxygen, sulfur, halogens, nitrogen, phosphorus, and the like.
[0110] Furthermore, in order to obtain an arbitrary discharge curve according to the application of the power storage device, the above-mentioned negative electrode materials can be mixed and used in a plurality of predetermined ratios.
[0111] The physical properties of the negative electrode material are determined by the requirements of the design and manufacturing process of the storage device (e.g., storage battery) due to the constraints such as the use of the storage device. In the manufacture of the material, the process design is performed in a manner that can achieve its physical properties. Examples of physical property values include powder particle size and distribution, specific surface area, density, etc.
[0112] For example, the powder particle size can be appropriately selected in consideration of other constituent elements of the power storage device, and is usually preferably 1 to 70 μm, more preferably 3 to 30 μm, as an average value from the viewpoint of improving battery characteristics such as rate characteristics and cycle characteristics.
[0113] The above-mentioned negative electrode materials generally have high electron conductivity, but in the case where the material has a smooth surface and the contact between the particles is insufficient, it is also preferred to coexist with a conductive auxiliary agent that assists electron conductivity. As the material, carbon-based materials, metal-based materials, and other materials with high electron conductivity can also be used, among which carbon-based materials are preferred.
[0114] The amount of the conductive auxiliary agent to be present is limited to the necessary minimum, and the content of the negative electrode material that specifies the capacity of the electricity storage device should be maximized.
[0115] Examples of conventional carbon-based materials include carbon black, acetylene black, Ketjen black, lamp black, furnace black, carbon black, graphite, carbon fiber, graphite fiber, nanofiber, nanotube, coke, hard carbon, and amorphous carbon.
[0116] Compared with these, as described above, the conductive auxiliary agent of this embodiment has major features not found in conventional materials, namely, it has a fine structure like nanocarbon, has elasticity against stress, and has a high specific surface area and a small number of oxygen-containing functional groups.
[0117] Due to this feature, even when the conductive agent is exposed to an electrochemical reduction environment or a stress environment in a battery, the electronic conductivity of the electrode can be maintained, thereby suppressing degradation of characteristics.
[0118] The preferred ratio of the conductive aid composed of the porous carbon material of the present invention contained in the negative electrode varies depending on the type of negative electrode material, the type and amount of the binder, the battery capacitor design, etc., but preferably each negative electrode mixture is 0.03wt% or more.
[0119] The metal foil for current collection is preferably a material that can be obtained cheaply and can withstand industrial use, and preferably a material that does not have electrochemical reactivity relative to the potential displayed by the negative electrode. For example, as the metal foil for current collection, copper foil, nickel foil, titanium foil, stainless steel foil are preferred, and electrolytic copper foil and rolled copper foil that are usually easily available are more preferred.
[0120] As a method for forming a coating film of the slurry, a commonly used printing technique can be used. When the thickness dimension is small, gravure printing or the like is preferably used, and when the thickness dimension is large, a printing method such as doctor blade printing or die printing is preferably used.
[0121] Thereafter, the coating film is dried by heating. Any drying method may be used, but it is preferable to use a method that can achieve a desired adhesive strength with the adhesive material.
[0122] Then, when the negative electrode is formed into a predetermined size, it is preferred to use an industrially available cutting blade or the like and its method. In addition, in order to achieve a predetermined density, it is preferred to use an industrially available pressurizing device or the like and its method as needed.
[0123] The above-mentioned negative electrode material and conductive aid are mostly in powder form. In order to fix them to each other and to the metal foil for current collection, a small amount of binding material is preferably mixed and used. The binding material is required to be chemically and electrochemically inactive and have some flexibility and affinity, and preferably a plastic resin material is used.
[0124] Examples of the plastic resin material include fluorine resins such as polyvinyl fluoride, polyvinylidene fluoride, and polytetrafluoroethylene, CN-containing polymers such as polyacrylonitrile and polyvinylidene fluoride, polyvinyl acetate and polyvinyl alcohol and other polyvinyl alcohol polymers, halogen-containing polymers such as polyvinyl chloride and polyvinylidene chloride, conductive polymers such as polyaniline, alkane polymers such as polyethylene, polypropylene, and poly-1,1-dimethylethylene, unsaturated polymers such as polybutadiene and polyisoprene, polymers having rings such as polystyrene, polymethylstyrene, polyvinylpyridine, and poly-N-vinylpyrrolidone, acrylic polymers such as polymethyl methacrylate, polyethyl methacrylate, polybutyl methacrylate, polymethyl acrylate, polyethyl acrylate, polyacrylic acid, polymethacrylic acid, and polyacrylamide, carboxymethyl cellulose, styrene-butadiene rubber, etc. In addition, the resin materials may be a mixture, a modified product, a derivative, a random copolymer, an alternating copolymer, a graft copolymer, a block copolymer, etc. The weight average molecular weight of these resins is usually 10,000 to 3,000,000, preferably 100,000 to 1,000,000. If the molecular weight is too small, the strength of the coating film decreases, and if it is too large, the viscosity increases, making it difficult to form an electrode.
[0125] In order to distribute the bonding material evenly and form the slurry coating into a predetermined size, a suitable slurry solvent that only dissolves the bonding material resin but does not dissolve other materials can be used. For example, in the case of using polyvinylidene fluoride, dimethylformamide is preferably used as the solvent. Alternatively, N-methylpyrrolidone can be used as the solvent, which can be appropriately selected and used according to the conditions of the manufacturing process.
[0126] The battery electrolyte of the present invention will be described. Electrolytes are prepared by dissolving solutes in organic solvents, and are usually the main components.
[0127] As one of the compositions of the electrolyte, first there is a solute which is a source of ions, that is, a Li salt.
[0128] The type of solute is not particularly limited, and any solute may be used as long as it is a solute known to be used for the purpose of the electricity storage device. Specific examples include the following.
[0129] Examples of solutes include inorganic salts such as LiPF6 and LiBF4, LiCF3SO3, LiN(CF3SO2)2, LiN(C2F5SO2)2, Li cyclic 1,2-perfluoroethanedisulfonimide, Li cyclic 1,3-perfluoropropanedisulfonimide, LiN(CF3SO2)(C4F9SO2), LiC(CF3SO2)3, LiPF4(CF3)2, LiPF4(C2F5)2, LiPF4(CF3SO2)2, LiPF4(C2F5SO2)2, LiBF2(CF3)2, LiBF2(C2F5)2, LiBF2(CF3SO2)2, LiBF2(C2F5SO2)2 and other fluorine-containing organic Li salts and Li bis(oxalato)borate, etc.
[0130] Among them, LiPF6, LiBF4, LiN(CF3SO2)2 and LiN(C2F5SO2)2 are preferred from the perspective of battery performance, and LiPF6 and LiBF4 are particularly preferred.
[0131] In addition, these Li salts may be used alone or in combination of two or more.
[0132] The content of the Li salt in the electrolyte varies depending on the type of solvent in which the Li salt is dissolved and the mixed composition, and is preferably 7 to 190 wt %, more preferably 10 to 180 wt %, and further preferably 13 to 150 wt %.
[0133] Next, the organic solvent used in the electrolyte is described.
[0134] Its kind is not particularly limited, and can be appropriately selected from the solvent known as solvent in the past. For example, cyclic carbonates, chain carbonates, cyclic ethers, chain ethers, cyclic carboxylates, chain carboxylates, phosphorus-containing organic solvents, etc., which do not have unsaturated bonds can be enumerated.
[0135] Factors that affect the movement of Li ions include the viscosity and solvation power of the organic solvent in addition to viscosity. The solvation power is the force that dissociates dissolved ions. If it is too strong, the movement of ions is hindered, so there is an optimal value.
[0136] In addition, practical power storage devices are used in a wide range of environmental conditions, especially the melting point, boiling point and other physical properties of organic solvents also need to be concentrated within a certain range.
[0137] In order to meet the above requirements, a practical solution is to use a mixture of multiple organic solvents. The composition of the mixture is determined by combining various physical properties such as organic solvents with high melting points and organic solvents with low melting points, organic solvents with high solvating power and organic solvents with low solvating power, etc., taking practical characteristics into consideration.
[0138] In the electrolyte of the present embodiment, it is preferred to use a mixture of a cyclic carbonate and a chain carbonate, both of which have no carbon-carbon unsaturated bond.
[0139] Examples of the cyclic carbonate include alkylene carbonates having an alkylene group having 2 to 4 carbon atoms, such as ethylene carbonate, propylene carbonate, and butylene carbonate. Among them, ethylene carbonate and propylene carbonate are preferred, and ethylene carbonate is particularly preferred from the viewpoint of improving battery characteristics.
[0140] As the chain carbonates, dialkyl carbonates are preferred, and the carbon number of the constituting alkyl group is preferably 1 to 5, particularly preferably 1 to 4. Specifically, examples thereof include symmetrical chain alkyl carbonates such as dimethyl carbonate, diethyl carbonate, and di-n-propyl carbonate; and asymmetrical chain alkyl carbonates such as ethyl methyl carbonate, methyl n-propyl carbonate, and ethyl n-propyl carbonate. Among them, dimethyl carbonate is the lowest and is preferred in terms of viscosity.
[0141] However, the boiling point of dimethyl carbonate is slightly low, so by further mixing and using the chain carbonates showing a higher boiling point, more suitable properties can be obtained. As the chain carbonate to be mixed, diethyl carbonate is preferred, but other chain carbonates can also be used without problem.
[0142] The mixing ratio varies depending on the desired practical properties. The ratio of the chain carbonate to the cyclic carbonate has an optimal composition including the ratio of the Li salt.
[0143] The content of the cyclic carbonate in the electrolyte is preferably 1 to 35% by weight, more preferably 3 to 30% by weight, and further preferably 4 to 25% by weight. A plurality of cyclic carbonates may be used in combination.
[0144] On the other hand, the content of the chain carbonate in the electrolyte is preferably 40 to 70% by weight, more preferably 43 to 68% by weight. The chain carbonate may be used in combination of two or more.
[0145] As a comprehensive composition, the following combination is preferred. In the combination of ethylene carbonate and dialkyl carbonate, ethylene carbonate and dimethyl carbonate are preferred, and symmetrical chain dialkyl carbonate and / or asymmetrical chain dialkyl carbonate may also be contained. For example, when containing ethylene carbonate, symmetrical chain dialkyl carbonate and asymmetrical chain dialkyl carbonate such as ethylene carbonate, dimethyl carbonate and diethyl carbonate, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate, the balance between the cycle characteristics and the high output discharge characteristics is good, so it is preferred. Among them, the asymmetrical chain dialkyl carbonate is preferably ethyl methyl carbonate, and the alkyl group of the alkyl carbonate preferably has 1 to 2 carbon atoms.
[0146] Furthermore, as a solvent that assists the dissociation and migration of ions, cyclic ethers, chain ethers, cyclic carboxylates, chain carboxylates, etc. may be added to the above-mentioned main organic solvents.
[0147] Examples of the cyclic ethers include tetrahydrofuran and 2-methyltetrahydrofuran, and examples of the chain ethers include dimethoxyethane and dimethoxymethane.
[0148] Examples of the cyclic carboxylic acid esters include γ-butyrolactone and γ-valerolactone, and examples of the chain carboxylic acid esters include methyl acetate, methyl propionate, ethyl propionate, and methyl butyrate.
[0149] Among them, chain carboxylic acid esters are particularly preferred.
[0150] Furthermore, it is also preferable that the electrolyte of the present embodiment contains a fluorine-containing cyclic carbonate having two or more fluorine atoms.
[0151] The number of fluorine atoms in the fluorine-containing cyclic carbonate having two or more fluorine atoms is not particularly limited, but in the case of fluoroethylene carbonate, the lower limit is usually 2 or more, and the upper limit is usually 4 or less, preferably 3 or less.
[0152] In the case of fluoropropylene carbonate, the lower limit is usually 2 or more, and the upper limit is usually 6 or less, preferably 5 or less. In particular, from the viewpoint of improving cycle characteristics and storage characteristics, it is preferred that two or more fluorine atoms are bonded to the carbon forming the ring structure.
[0153] Among them, from the viewpoint of improving battery characteristics, fluoroethylene carbonate having two or more fluorine atoms is preferred, and among them, cis-4,5-difluoro-1,3-dioxolane-2-one, trans-4,5-difluoro-1,3-dioxolane-2-one, and 4,4-difluoro-1,3-dioxolane-2-one are particularly preferred.
[0154] The fluorinated cyclic carbonate with more than 2 fluorine atoms can be used alone, or more than 2 kinds can be used in combination. In order to show the effect of the present embodiment, the ratio of the fluorinated cyclic carbonate compound with more than 2 fluorine atoms in the non-aqueous electrolyte is not particularly limited, usually more than 0.001 weight %, preferably more than 0.01 weight %, more preferably more than 0.1 weight %, particularly preferably more than 0.2 weight %, most preferably more than 0.25 weight %. At a concentration lower than it, it is sometimes difficult to show the effect of the present embodiment. On the contrary, if the concentration is too high, then the internal pressure of the battery increases when the high temperature is preserved sometimes, so the upper limit is usually below 10 weight %, preferably below 4 weight %, more preferably below 2 weight %, particularly preferably below 1 weight %, most preferably below 0.5 weight %.
[0155] In addition, cyclic carbonates having an unsaturated bond and aromatic compounds having a total carbon number of 7 to 18 may be mixed in the electrolyte for use.
[0156] In the cyclic carbonates with unsaturated bonds, from the viewpoint of improving cycle characteristics, preferably vinylene carbonate, vinyl ethylene carbonate, 4-methyl-4-vinyl ethylene carbonate or 4,5-divinyl ethylene carbonate, wherein, more preferably vinylene carbonate or vinyl ethylene carbonate. They can be used alone, or two or more can be used in combination.
[0157] Examples of the aromatic compound having a total carbon number of 7 to 18 include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, tert-butylbenzene, tert-amylbenzene, diphenyl ether, and dibenzofuran.
[0158] It is considered that by suppressing the side reaction of the aromatic compound having a total carbon number of 7 or more and 18 or less with the negative electrode and the positive electrode, a significant decrease in discharge characteristics after high-temperature storage is suppressed.
[0159] In order to show the effect of the present embodiment, the total carbon atoms in the electrolyte are more than 7 and the ratio of the aromatic compounds below 18 is usually more than 0.001 weight %, preferably more than 0.1 weight %, particularly preferably more than 0.3 weight %, most preferably more than 0.5 weight %, and the upper limit is usually less than 5 weight %, preferably less than 3 weight %, particularly preferably less than 2 weight %. When concentration is lower than the lower limit, it is sometimes difficult to show the effect of safety when improving overcharge. On the contrary, when concentration is too high, the characteristics of batteries such as high temperature storage characteristics are reduced sometimes.
[0160] The separator 215 separates the positive electrode 212 from the negative electrode 214 to prevent short circuit of current caused by contact between the two electrodes and allows lithium ions to pass through. A porous film made of resin is preferably used.
[0161] As the form of the film, it is preferable to use a stretched film in which pores are formed by stretching a bulk resin, a nonwoven fabric having a porous structure such that a porous film can be produced by laminating a large number of fibrous resin fibers, or the like.
[0162] As the material of the resin, polyolefins can be cited, and polyethylene is particularly preferred. Polyethylene has a relatively low melting point. When the temperature of the battery rises due to some reason (for example, unsafe conditions such as short circuit, etc.), the pores in the membrane are blocked due to thermal melting, hindering the movement of driving ions, thereby stopping the reaction and ensuring safety.
[0163] A porous film formed by stretching is usually formed by adding a plasticizer to polyolefin, removing the plasticizer before or after stretching, and the portion where the plasticizer exists becomes a base point, thus having a relatively uniform microporous structure.
[0164] When producing a stretched film, stretching is usually performed in both the longitudinal direction and the width direction. A suitable stretched film can be obtained by removing the above-mentioned plasticizer and the like and appropriately combining any atmosphere medium, temperature, speed, stress, number of process repetitions, etc.
[0165] The above-mentioned production process can obtain a high-quality stretched film, but it is a multi-step process, so it is difficult to reduce production costs such as process costs, which may become a negative factor in the popularization of power storage devices.
[0166] On the other hand, by simplifying the process by stretching only in the longitudinal direction without using a plasticizer, a porous membrane that can be manufactured at an industrial level and can reduce the manufacturing cost can be obtained. The resin that can be applied in this case is a polyolefin, preferably polypropylene.
[0167] The separator between the positive electrode and the negative electrode can be formed by an electrically insulating porous body. As a separator, for example, a film or fiber nonwoven fabric made of a polymer such as polyolefins such as polyethylene and polypropylene, polyester, polyethylene terephthalate, polyimide, etc. can be applied. The material of the separator can be used alone or in multiple forms. In addition, the separator can be a single layer or a multilayer (composite film). In addition, the separator can contain inorganic material nanoparticles such as ceramics. In addition, a polymer compound such as polyvinylidene fluoride can also be applied to both sides of the separator.
[0168] In the non-aqueous electrolyte battery of the present embodiment, an electrolyte that becomes gel-like by including a polymer compound can also be used, and the polymer compound is swollen by an organic solvent to become a retainer for retaining a non-aqueous electrolyte. This is because, by including a polymer compound swollen by an organic solvent, a high ion conductivity can be obtained, an excellent charge and discharge efficiency can be obtained, and leakage of the battery can be prevented. In the case of containing a polymer compound in a non-aqueous electrolyte, the content of the polymer compound is preferably set to a range of more than 0.1 mass % and less than 10 mass % of the non-aqueous electrolyte.
[0169] When a polymer compound such as polyvinylidene fluoride is coated on both sides of the separator, the mass ratio of the nonaqueous electrolyte to the polymer compound is preferably within a range of 50:1 to 10:1. Within this range, higher charge and discharge efficiency can be obtained.
[0170] As the above-mentioned macromolecular compound, for example, ether macromolecular compounds such as polyvinyl formal, polyethylene oxide and crosslinked bodies containing polyethylene oxide, ester macromolecular compounds such as polymethacrylate, acrylate macromolecular compounds and polyvinylidene fluoride, and polymers of vinylidene fluoride such as copolymers of vinylidene fluoride and hexafluoropropylene can be listed. The macromolecular compound can be used alone or in combination. In particular, from the viewpoint of preventing the swelling effect during high temperature storage, fluorine-based macromolecular compounds such as polyvinylidene fluoride are preferably used.
[0171] The power storage device having the above-described configuration functions as follows. When the power storage device is charged, Li ions contained in the positive electrode 212 are inserted into the interlayers of the layered structure of graphite contained in the negative electrode 214 through the separator 215. Thereafter, when the power storage device is discharged, the Li ions are separated from the interlayers of the layered structure contained in the negative electrode 214 and return to the positive electrode 212 through the separator 215.
[0172] In the above, the power storage device according to one embodiment of the present invention has been described by taking a lithium ion battery as an example, but the present invention is not limited to the above embodiment and various modifications are possible without departing from the gist of the invention.
[0173] In the above embodiment, a coin-shaped lithium-ion battery is used as an example of an electric storage device, but the electric storage device of this embodiment is also applicable to electric storage devices having other shapes such as button-shaped, paper-shaped, square-shaped, or cylindrical-shaped with a spiral structure. In addition, the electric storage device of this embodiment can be made into various sizes such as thin and large.
[0174] Furthermore, in the above description, an embodiment is described in which a liquid electrolyte is assumed as the electrolyte of the power storage device of this embodiment, but any other electrolytes can be applied, and as an example, a gel electrolyte or a solid electrolyte can also be preferably used. Example
[0175] Hereinafter, examples of the present embodiment will be described. The present invention is not limited to the following examples. First, examples of the carbon material of the present embodiment will be described.
[0176] [Example 1] (Mold) First, Kyowamag (registered trademark) MF-150 was prepared as a porous casting mold. As confirmed in Production Example 1 described later, Kyowamag (registered trademark) MF-150 is a powder containing a porous body composed of magnesium oxide. Figure 8 This is an electron microscope image of the porous casting mold used in Example 1. The porous casting mold used in Example 1 has a plurality of primary particles stacked on top of each other.
[0177] (Heat treatment process and coating process) Using the prepared porous mold, a heat treatment process and a coating process are carried out to coat the porous mold with a carbon layer to obtain a molded product. In Example 1, first, as a heat treatment process, the porous mold is heat treated at 900°C for 30 minutes after heating at a heating rate of 10°C / min in an argon atmosphere. Next, in the coating process, the same device as the heat treatment process is used to continuously perform chemical vapor growth for 2.5 hours at a flow rate of 80ml / min and 320ml / min at 900°C with methane as a raw material gas and argon as a process gas. After that, the flow rate of the methane gas is set to 0ml / min and maintained for 30 minutes, and then naturally cooled to room temperature.
[0178] (Separation process) Next, 2 g of the molded product obtained by the coating process and 100 g of 5 mol / L hydrochloric acid were placed in a beaker for mixing and stirred at room temperature for 5 hours at 600 rpm. Then, the separated molded product was taken out from the porous mold, and the sample was filtered using a membrane filter (0.1 μm) while being washed 5 times with pure water, and suction filtration was performed. Afterwards, the molded product and hydrochloric acid were mixed and stirred again by the same method as before, and the molded product was suction filtered using pure water.
[0179] Next, the molded product is placed in a threaded tube bottle containing 100mL of acetone, covered with a lid, and shaken thoroughly. Then, it is allowed to stand overnight at 60°C in a constant temperature dryer. The next day, the supernatant is discarded, 100mL of acetone is added again, and it is allowed to stand at 60°C in a constant temperature dryer for 3 hours. Next, the supernatant is discarded, 100mL of acetone is added again, and it is allowed to stand at 60°C in a constant temperature dryer again for 3 hours. After that, the acetone is removed by suction filtration, and a constant temperature dryer is used to perform reduced pressure drying at 150°C, 10 hours, and below 1000Pa twice, thereby making a CMS (mesoporous carbon sponge) made of a carbon material.
[0180] [Example 2] Example 2 is different from Example 1 in that a stabilization step is performed after the separation step. The other steps are the same as those of Example 1.
[0181] (Stabilization process) The separation process is followed by a stabilization process. Specifically, CMS is placed in a sample chamber of a high-temperature heating furnace (manufactured by Izumi Electric Co., Ltd., IZU-SMS005), the sample chamber is evacuated, and the temperature is raised to 1800°C at a rate of 15°C / min while argon gas is flowing at 10 ml / min, and heat-treated at 1800°C for 1 hour, thereby sintering CMS to produce GMS (graphene mesoporous sponge).
[0182] [Production Example 1] Production Example 1 refers to a stage of a casting mold of Kyowamag (registered trademark) MF-150, which is a porous casting mold used in Example 1.
[0183] [Production Example 2] Manufacturing Example 2 refers to a mold in which the porous mold used in Example 1 was subjected to a heat treatment step under the same conditions as in Example 1. That is, Kyowamag (registered trademark) MF-150 was heated to 900°C at a heating rate of 10°C / min in an argon atmosphere, and then the porous mold was heat treated at 900°C for 30 minutes.
[0184] [Production Example 3] Manufacturing Example 3 refers to a product obtained by subjecting the porous casting mold used in Example 1 to a heat treatment process and a coating process under the same conditions as in Example 1. That is, after being treated under the same conditions as in Manufacturing Example 2, the same apparatus as in the heat treatment process was used to perform chemical vapor growth at 900° C. for 2.5 hours with methane as a raw material gas and argon as a process gas at flow rates of 80 ml / min and 320 ml / min, respectively, continuously with the heat treatment process, and then the flow rate of the methane gas was set to 0 ml / min, maintained for 30 minutes, and naturally cooled to room temperature.
[0185] [Comparative Example 1] As Comparative Example 1, GMS (graphene mesoporous sponge) was prepared by the same process as in Example 2, except that alumina nanoparticles (product name: SBa-200, manufactured by Sasol Chemical, primary particle size: 7 nm) were used as the casting mold and 46% hydrofluoric acid was used instead of hydrochloric acid in the separation step to dissolve the casting mold for 4 hours.
[0186] [Comparative Example 2] As Comparative Example 2, GMS (graphene mesoporous sponge) was prepared by the same process as Comparative Example 1 except that alumina nanoparticles (product name: TM-100, manufactured by Daimei Chemical Industry Co., Ltd., primary particle size: 14 nm) were used as the mold.
[0187] [Comparative Example 3] As Comparative Example 3, GMS (graphene mesoporous sponge) was prepared by the same process as Comparative Example 1 except that alumina nanoparticles (product name: TM-300, manufactured by Daimei Chemical Industry Co., Ltd., primary particle size: 7 nm) were used as the mold.
[0188] The conditions of Production Examples 1 to 3, Example 1, Example 2, and Comparative Examples 1 to 3 are summarized in the following Table 1. MF-150 is a porous casting mold having a primary particle diameter of 300 nm to 30 μm.
[0189] [Table 1]
[0190] (SEM observation) The porous carbon materials of Examples 1 and 2, the porous casting mold of Preparation Example 2, the molded product of Preparation Example 3, and the carbon material of Comparative Example 1 were observed using a scanning electron microscope. Each sample was photographed at the same magnification (30,000 times, 100,000 times) at an accelerating voltage of 1.0 kV. Fig.9A and Fig. 9B , Fig. 10A and Fig. 10B , Fig.11A and 11B , Fig. 12A and Fig. 12B , Fig.13 These are SEM images of the porous casting mold of Manufacturing Example 2, the molded product of Manufacturing Example 3, the porous carbon material of Example 1, the porous carbon material of Example 2, and the carbon material of Comparative Example 1, respectively. Fig.9A and Figures 9B to 12A and Fig. 12B In the figure, "A" represents the SEM image at 30,000 times magnification, and "B" represents the SEM image at 100,000 times magnification. Fig.9A and Figures 9B to 12A and Fig. 12B It was confirmed that by using a plate-shaped porous mold, primary particles of a porous carbon material having a plate-shaped shape corresponding to the shape of the primary particles of the porous mold were formed. Fig.13 In the experiment, a structure with large particle size and multiple particles was formed, indicating that the nanoparticles underwent secondary aggregation.
[0191] according to Fig.11A and Fig. 11B as well as Fig. 12A and Fig. 12B , the primary particle size of porous carbon materials can be identified. Fig.11A , Fig. 12A In the same 30,000x SEM image, 100 electron beams intersecting the main surface of the porous carbon material are observed. Fig.11A and Fig. 11B In the main surface, the major diameter in the long side direction is 200 to 1000 nm, with an average value of 400 nm, and the minor diameter in the short side direction perpendicular to the long side direction is 150 to 500 nm, with an average value of 300 nm. Fig. 12A and Fig. 12B In the embodiment 1, the long diameter in the long side direction is 200 to 1000 nm, and the average value is 400 nm. The short diameter in the short side direction orthogonal to the long side direction is 150 to 500 nm, and the average value is 300 nm. That is, the average value of the in-plane length of the primary particles of these porous carbon materials, that is, the primary particle size of the porous carbon materials is 400 nm. In addition, the thickness of the porous carbon materials whose in-plane length was measured was 100 nm in Example 1 and 100 nm in Example 2.
[0192] (Based on TEM observation) The shapes of the porous carbon materials of Examples 1 and 2, the porous casting mold of Manufacturing Example 2, and the molded product formed by coating the porous casting mold with a carbon layer of Manufacturing Example 3 were observed using a transmission electron microscope (JEM-2010, JEOL.) The porous carbon materials were observed using a transmission electron microscope at an accelerating voltage of 200 kV. Fig.14A and Fig. 14B , Fig.15A and Fig. 15B , Fig.16A and Fig. 16B , Fig.17A and Fig. 17B TEM images of Production Example 2, Production Example 3, Example 1, and Example 2 are shown, respectively.
[0193] Fig.17A and Fig.17A B is a view of the vicinity of the end of the porous carbon material. Fig. 17BIn the figure, the parts that appear to be a single layer are marked with the reference numeral A, and the parts that appear to be multiple layers are marked with the reference numeral B. Fig. 17B It can be confirmed that a single layer of graphene is formed at the end of the sample, but there are also parts where two to three layers of graphene are deposited depending on the location.
[0194] (Particle size distribution) For the porous carbon materials of Example 1 and Example 2, the porous molds of Manufacturing Example 1 and Manufacturing Example 2, and the molded product in which the carbon layer of Manufacturing Example 3 is coated with the porous mold, a laser diffraction particle size distribution measuring device (Microtrac BEL Co., Ltd., MT3300 EXII-SDC) is used to measure the particle size distribution. Specifically, for Manufacturing Example 1, Manufacturing Example 2, and Manufacturing Example 3, ethanol is mixed with a solvent before measurement, and a three-frequency ultrasonic cleaner (AS ONE Co., Ltd., VS-100III) is used to perform ultrasonic treatment for 5 minutes, and then the particle size distribution is measured using the above-mentioned device. In addition, for Example 1 and Example 2, ethanol is mixed in a solvent before measurement, and after 30 minutes of ultrasonic treatment using a three-frequency ultrasonic cleaner (AS ONE Co., Ltd., VS-100III), the particle size distribution is measured using the above-mentioned device. In addition, for the porous carbon material of Example 2, the following sample (Example 2-B) was also prepared: after the porous carbon material was made according to the same process, it was used with a high-frequency ultrasonic cleaner (VS-100III manufactured by AS ONE Co., Ltd.) for 30 minutes, and then dispersed with an ultrasonic homogenizer (VCX-750 manufactured by SONICS Corporation) for 10 minutes.
[0195] Fig.18 The particle size distribution of the porous carbon materials of Example 1, Example 2 and Example 2-B, the porous molds of Manufacturing Example 1 and Manufacturing Example 2, and the molded product of Manufacturing Example 3. As shown in Figure 15, it is confirmed that the particle size distribution of the porous carbon material is larger than that of the porous mold. The particle size distribution of the porous carbon material of Example 1 is about 370nm to about 4μm, and its peak is about 1.6μm. In addition, the particle size distribution of the porous carbon material of Example 2 is about 1μm to 20μm, and its peak is about 6.5μm. The particle size distribution of Example 2-B is about 0.9μm to 11μm, and its peak is about 2.5μm. Comparing Example 2 and Example 2-B, which are porous carbon materials prepared under the same conditions, it is confirmed that the particle size distribution changes significantly due to dispersion. It is confirmed that the porous carbon materials prepared in these examples are plate-like in shape and the interaction between the primary particles is small, so even if agglomeration occurs during production, the individual particles can be separated.
[0196] Fig.19The particle size distribution of the porous carbon materials of Example 2 and Example 2-B and the carbon materials of Comparative Examples 1 to 3. For Comparative Example 3, an ultrasonic homogenizer (VCX-750 manufactured by SONICS) was used to disperse the particles for 30 minutes. Fig.19 It can be confirmed that the porous carbon materials of Example 2 and Example 2-B have smaller values of particle size distribution than the carbon materials of Comparative Examples 1 to 3. In addition, the particle size distribution of Comparative Example 1 is about 12 μm to 250 μm, with a peak of about 52 μm, the particle size distribution of Comparative Example 2 is about 5 μm to 420 μm, with a peak of about 150 μm, and the particle size distribution of Comparative Example 3 is about 1.5 μm to 350 μm, with a peak of about 135 μm.
[0197] The particle size of TM-300 used as a mold in Comparative Example 3 (secondary particle size formed by agglomeration of nanoparticles) is about the same as the particle size of TM-100 used as a mold in Comparative Example 2 (secondary particle size formed by agglomeration of nanoparticles). In Comparative Example 2, ultrasonic dispersion was not performed, whereas in Comparative Example 3, dispersion was performed using an ultrasonic homogenizer, but Fig.19 , the particle size distribution of Comparative Example 3 is substantially the same as that of Comparative Example 2. Therefore, unlike the examples, it is considered that the carbon material of the comparative example is difficult to eliminate aggregation.
[0198] (XRD measurement) For the porous carbon materials of Examples 1 and 2, and the porous casting molds of Manufacturing Examples 1 and 2, XRD (X-ray diffraction) measurements were performed using an X-ray diffraction device manufactured by Rigaku Corporation (Rigaku Corporation, Miniflex 600). A Si non-reflective plate was used as the sample stand, and the sample was placed on the circular portion for measurement. The measurement conditions are summarized in Table 2.
[0199] [Table 2] X-ray Source CuKα Tube voltage 40kV Tube Current 15mA Determination angle 2~90 degrees. Scan speed 5deg. / min Scan axis 2θ / θ
[0200] Fig. 20A and 20B The XRD analysis results of Production Examples 1 and 2 are shown in FIG. Fig. 20B Yes Fig. 20A The analysis results of Production Example 1 and Production Example 2 are shown in a superimposed graph so that the magnitudes of the vertical axes are aligned. Fig. 20B The peak of magnesium hydroxide is also shown. Fig. 20A and 20B As shown in FIG. 1 , in the XRD analysis result of the porous casting mold before the heat treatment step, the peak of magnesium hydroxide that is not seen in the XRD analysis result of the porous casting mold after the heat treatment step is confirmed. Therefore, it can be seen that magnesium hydroxide is separated by the heat treatment step. The reason for this is examined together with the results of the TG analysis described later.
[0201] Fig.21 The XRD analysis results of Example 1 and Example 2 are shown. In Example 1 and Example 2, the 002 peak near 25° from the stacking structure of graphene and the 10 peak near 43° from the sheet structure of graphene are confirmed. Therefore, it is confirmed that the porous carbon materials of Example 1 and Example 2 both have a graphene skeleton. In Example 1 and Example 2, it is believed that the 002 peak is flat and no multi-layer stacking of graphene is produced. It is also known that in Example 2 that has undergone a stabilization process, the intensities of the 10 peaks and 11 peaks from the sheet structure of graphene are higher than the peak intensity in Example 1, and the sheet structure of graphene grows through the stabilization process. It should be noted that, regarding the 11 peak, it was not confirmed in Example 1.
[0202] (Raman spectroscopy) Raman spectra of the porous carbon materials of Example 1 and Example 2 were measured using a Raman microscope (Lab RAMHR-800, manufactured by Horiba, Ltd.). The measurement was performed using a 532 nm laser, a filter set to D1, and an aperture set to 100 μm. The measurement range was 300 to 3500 cm -1 . Fig. 22 It is the Raman spectra of Example 1, Example 2 and HOPG.
[0203] In both Example 1 and Example 2, the presence of D and D' bands originating from defects such as non-hexagonal sites containing edge sites, G bands originating from skeleton vibrations of graphene sheets, and 2D bands based on secondary phonon scattering were confirmed. The D band appears as a hexagonal leakage mode at the site where the hexagonal symmetry of the graphene mesh is broken. The D' band is a hexagonal variable angle mode, which is prohibited in an infinitely wide hexagonal mesh. Therefore, it is also confirmed by Raman spectroscopy that the porous carbon materials of Example 1 and Example 2 also have a graphene skeleton. In addition, in either Example 1 or Example 2, the 2D peak exists on the low-lying layer side compared to the 2D peak of HOPG, and can be fitted with a single Lorentzian function, so it can be seen that in Example 1 and Example 2, single-layer graphene grows. In addition, in Example 1, the mesh size is sometimes small and the 2D peak intensity is small compared to Example 2.
[0204] (Nitrogen adsorption-desorption measurement) The porous carbon materials of Examples 1 and 2, the porous casting molds of Examples 1 and 2, and the molded product formed by the carbon layer covered by the porous casting mold of Example 3 were subjected to nitrogen adsorption and desorption measurement using an automatic specific surface area / pore distribution measuring device (BELSORP mini, Japan BEL Co., Ltd.). The samples were dried under reduced pressure at 150° C. for 6 hours using BELpre before the measurement.
[0205] Fig.23 1 and 2 are nitrogen adsorption-desorption curves of the porous carbon materials of Examples 1 and 2. Fig.24 The nitrogen adsorption-desorption curves are those of the porous molds of Production Examples 1 and 2 and the molded product of Production Example 3.
[0206] according to Fig.23 The nitrogen adsorption isotherms shown in the figure are used to calculate the BET specific surface area of the porous carbon materials of Example 1 and Example 2 using the BET method. The applicable range of the BET method is P / P0=0.05-0.3. The specific surface areas of the porous carbon materials of Example 1 and Example 2 are 1780 (m 2 / g) and 2060(m 2 / g). That is, it was confirmed that the specific surface area of the porous carbon material was greatly increased by the process of stabilizing the porous carbon material. In addition, the specific surface area of Comparative Example 1 was measured by the same method and the result was 2010 (m 2 / g).
[0207] Regarding the adsorption-desorption isotherm, a type IV isotherm with hysteresis was obtained, and the presence of mesopores can be confirmed. In both Example 1 and Example 2, the rise of the isotherm can be confirmed in the region of P / P0≥0.9, and there may be macropores. In addition, in the isotherm of Example 2, the rise in the region near P / P0=0.97 becomes larger than that of Example 1, so it is considered that micropores grow by sintering.
[0208] according to Fig.23 and Fig.24 The nitrogen adsorption isotherms shown in FIG. 1 and FIG. 2 were used to determine the pore size distribution using the BJH method for the porous carbon materials of Examples 1 and 2, the porous molds of Production Examples 1 and 2, and the molded product of Production Example 3. As the t file for calculating the pore size distribution, the GCB file was used. Fig.25 The pore size distribution of the porous casting molds of Manufacturing Example 1 and Manufacturing Example 2 and the molded product of Manufacturing Example 3, Fig.26 1 and 2 are the pore size distributions of the porous carbon materials of Examples 1 and 2.
[0209] Depend on Fig.25 It can be seen that the pore diameters of manufacturing examples 2 and 3 are larger than those of manufacturing example 1. Therefore, the pore diameter db of the porous casting mold increases during the heat treatment process. Fig.26 and Fig.25 By comparison, it can be seen that the pore diameter da of the porous carbon material is smaller than the pore diameter db of the porous mold. This is considered to be because the porous carbon material undergoes capillary contraction when the carbon layer is separated from the porous mold using an acid in the separation step. Fig.26 By comparing Example 1 and Example 2, it can be seen that the pore size distribution of the porous carbon material hardly changes before and after the stabilization step.
[0210] In addition, the BET specific surface areas of the porous casting molds of Manufacturing Examples 1 and 2 were calculated by the same method as in Example 1, and the results were 105 (m 2 / g)、86(m 2 / g).
[0211] (Average skeleton thickness) For the porous mold of Manufacturing Example 2, the BET specific surface area of the porous mold introduced into the above-mentioned formula (2) and the density of magnesium oxide 3.58 [g / cm 3 ], and calculated the average skeleton thickness of Production Example 2. The average skeleton thickness of the porous casting mold of Production Example 2 was 19.5 nm. d = 6.0 × 10 23 / (S×ρ)···(2) (where d represents the average skeleton thickness [nm], and ρ represents the density of the material constituting the porous mold [g / cm 3 ], S represents the BET specific surface area of the porous mold [m 2 / g]. )
[0212] (TG analysis) The porous carbon materials of Examples 1 and 2, the porous mold of Production Example 1, and the molded product of Production Example 3 were measured under air circulation using a thermogravimetric measuring apparatus (TGA-50, manufactured by Shimadzu Corporation) and a Pt pan. The measurement results were then corrected using the measurement data of an empty pan.
[0213] Fig. 27 This is the TG curve of the porous casting mold of Production Example 1. Fig. 27 The TG curve shown is data obtained when the temperature rise rate in the TG analysis was set to 10°C / min. Fig. 27 The TG curve of the porous mold shown in FIG. 20 shows that a weight loss of about 14% occurs by heating the porous mold at 900°C. In addition, it can be seen that a sharp weight loss is shown near 100°C. In the XRD pattern of the porous mold shown in FIG. 20 above, if it is considered that a peak of Mg(OH)2 is confirmed in Manufacturing Example 1 before heat treatment but not in Manufacturing Example 2 after heat treatment, it is believed that the weight loss of the porous mold is due to the decomposition of magnesium hydroxide and the detachment of moisture physically adsorbed in the air of the mold. In addition, it is believed that this is accompanied by the generation of Fig.25 As shown in the figure, the pore diameter increases and the specific surface area increases.
[0214] Fig.28 This is the TG curve of the molded product of Production Example 3. Fig.28 The TG curve shown is data obtained when the temperature increase rate in the measurement was set to 10° C. / min in the TG analysis. Fig.28The vertical axis in TG represents the ratio (%) of the weight of the sample at a predetermined temperature in the TG measurement to the weight of the sample before heating for the TG measurement.
[0215] exist Fig.28 In the TG curve shown in the figure, the carbon loading W is calculated. carbon (g / g). The amount of carbon starts to decrease gradually from 100°C due to water and other factors other than carbon, but the slope becomes gentler around 300°C, so the carbon content is calculated based on 300°C as the difference in weight (%) from the high temperature after combustion (780°C). The carbon loading is calculated from the difference of 98.76% at 300°C and 91.71% at 780°C, which is 7.05, to obtain 7.58%.
[0216] Here, the carbon loading amount W at each temperature is carbon (g / g) The following formula (3) was introduced to calculate the average number of stacked carbon layers N covering the porous mold. carbon (g / g) refers to the weight of carbon attached to 1g of the porous mold. graphene is 7.614×10 -4 g / m 2 , S template The measured value of manufacturing example 2 is 86 m 2 At 300° C., it was confirmed that the average number of stacked carbon layers was 1.12 layers, and single-layer graphene was formed in most of the region.
[0217] [Number 2] (In formula (3), W M : The amount of carbon deposited per unit area of the porous mold (g / m 2 ), W graphene : Weight per unit area of single-layer graphene (g / m 2 ), W carbon : Carbon loading (g / g) obtained from TG curve, S template : Specific surface area of porous mold (m 2 / g))
[0218] Fig.29 TG curves of the porous carbon materials of Example 1 and Example 2. Fig.29 The TG curve shown is data obtained by setting the temperature increase rate during the measurement to 5°C / min in the TG analysis. Fig.29It can be seen that in Example 2, the oxidation resistance is improved compared with Example 1 by undergoing a stabilization process. After TG analysis, white ash believed to be magnesium oxide used in the mold was confirmed in the porous carbon material of Example 1. The ash after TG analysis was 0.9wt% of the porous carbon material before TG analysis. The change before and after TG analysis calculated from the actual weight change measured using a microbalance was 1.0wt%. It was visually confirmed that the ash content of Example 2 was less than that of Example 1. In addition, the sample for which the ash content was measured was a different sample from the sample for which the oxidation resistance was measured, and the difference was that the heating rate in the TG analysis was set to 10°C / min.
[0219] Fig.30 This is a diagram showing the TG curve of the porous carbon material of Example 2 together with the TG curves of other carbon materials. Fig.30 The TG curve shown is data obtained by setting the temperature rise rate during measurement to 5°C / min in TG analysis. Fig.30 In the figure, XC72, KB, DB, BP, YP50F, and HOPG represent VULCAN XC72 (Cabot Co.), Ketjenblack EC300J (Lion Specialty Chemicals Co., Ltd.), BLACK PEARLS2000 (Cabot Co.), YP50F (Kuraray Co., Ltd.) as steam-activated activated carbon, and highly oriented thermally decomposed graphene, respectively. For these carbon materials, TG analysis was performed in the same manner as in Examples 1 and 2. It was confirmed that the porous carbon material of Example 2 is a carbon material with excellent oxidation resistance second only to HOPG. That is, these carbon materials heat the mixture, and the carbon material remaining at the end is the same porous carbon material (GMS) or HOPG as in Example 2.
[0220] (Temperature Desorption Analysis_TPD) If the carbon material is heated to 1800°C, the edge sites terminated with hydrogen and oxygen decompose into H2, CO, CO2, and H2O. Therefore, by measuring the release of these gases, the total amount of edge sites of the carbon material can be estimated. In the temperature desorption analysis, the porous carbon materials of Examples 1 and 2 were accurately qualitatively and quantitatively analyzed using an ultra-high sensitivity vacuum TPD device (developed by Northeastern University, see T. Ishii et al. CARBON 80, 2014, 135-145) for oxygen-containing functional groups and hydrogen-terminated edge sites. Fig.31: This is a diagram illustrating an ultra-high sensitivity vacuum TPD device 50 used in Example 1 and Example 2. The ultra-high sensitivity vacuum TPD device 50 comprises: a quartz reactor including a radioactive thermometer 41, a sample holder 42 and a high-frequency induction coil 43, and a detection unit connected to the quartz reactor. The detection unit comprises, for example, a gas reservoir, a turbomolecular pump TMP, a rotary pump RP, a cold cathode Pirani vacuum gauge P1, and an electrostatic capacitance gauge P2. Specifically, by the method described in the above-mentioned document, 1 to 3 mg of each porous carbon material is added to a sample holder composed of graphite, and vacuum heated to 1800°C at a heating rate of 10°C / min, and the gas released during heating is analyzed by mass analysis.
[0221] Fig.32A and Fig.32B The gas emission patterns when temperature desorption analysis was performed on Example 1 and Example 2 are shown. Fig.32A is the result of Example 1, Fig.32B This is the result of Example 2. It can be seen that the gas emission in Example 2 (0.11 mmol / g) is less than 5% of the gas emission in Example 1 (2.4 mmol / g), which is very small. After the stabilization process, the amount of edge sites is greatly reduced. That is, even when a high voltage is applied, the electrolyte is difficult to decompose, which can increase the energy density.
[0222] (Total pore volume) For the porous carbon material of Example 2, the nitrogen adsorption amount at the relative pressure P / P0=0.96 at -196°C was converted into the volume of liquid nitrogen density based on the adsorption-desorption isotherm, and the total pore volume was determined. The measurement results are shown in Table 3 together with the results of the carbon material made by the same method as in Comparative Example 2 using a mold of secondary particles of aluminum oxide nanoparticles and the carbon material made by the same method as in Comparative Example 1 using a mold of secondary particles of magnesium oxide nanoparticles and the BET specific surface area. It can be seen from Table 3 that compared with the previous carbon materials, the specific surface area and the total pore volume of Example 2 are increased. The literature value (Al2O3 secondary particle mold) and the literature value (MgO secondary particle mold) are based on the results of H.Nishihara et al.Adv.Funct.Mater., 2016, 26, 6418-6427., S.Sunahiro et al.J.Mater.Chem.A., 2021, 9, 14296-14308.
[0223] [Table 3]
[0224] [Example 3] A porous carbon material was prepared in the same manner as in Example 1 except that Kyowamag (registered trademark) MF-30 (BET specific surface area 24 m 2 / g) and Kyowamag (registered trademark) MF-150 (BET specific surface area 119m 2 That is, in Example 3, a porous carbon material was prepared by subjecting a porous casting mold Kyowamag (registered trademark) MF-30 to a heat treatment step, a coating step, and a separation step under the same conditions as in Example 1.
[0225] As an analysis of Example 3, first, the average skeleton thickness of the porous casting mold of Example 3 after the heat treatment step was calculated and the result was 69.8 nm.
[0226] Next, nitrogen adsorption and desorption measurements were performed in the same manner as in Example 1 to calculate the specific surface area and pore diameter. The specific surface area of the porous carbon material in Example 3 was 1200 m 2 / g, and the peak of the pore size distribution is 7.3nm. It is believed that the reason why the specific surface area of the porous carbon material in Example 3 is small is that the average skeleton coarseness of the porous casting mold used in Example 3 is coarse, and thus the carbon skeleton of the carbon layer coated on the casting mold is soft and very susceptible to the capillary contraction in the separation process.
[0227] <Diffusion resistance> (Example 4-1) Use a pestle and mortar to mix the porous carbon material of Example 2 as an active material, DENKABLACK as a conductive aid, and polytetrafluoroethylene (PTFE) as a binder in a weight ratio of 90:5:15 to make a paste. Next, two 1cm×1cm, 5mg molded bodies formed by the paste are molded. Next, the molded body is clamped with a Pt mesh and pressed with a manual press at a display pressure of about 3KN to make an electrode. Prepare two of these electrodes in a way that they have the same weight ratio, as the positive electrode and the negative electrode, respectively. After the prepared electrodes are dried at 120°C under vacuum for one night, button batteries are assembled in a glove box under an argon atmosphere.
[0228] The assembly of button batteries is to stack and accommodate the spring, spacer, electrolyte, negative electrode, diaphragm (glass fiber), electrolyte, positive electrode, electrolyte and spacer in the stacking direction between the outer body. The assembly of button batteries is to gently tighten the electrodes and diaphragms, and then crimp them using a dedicated assembly tool (Hosen, model: HSMCC-H10). As the electrolyte, 1M Et4NBF4 / PC is used.
[0229] For the button cells, electrochemical measurements were performed using a potentiostat (Bio-Logic: VMP3). Specifically, after standing in a thermostat at 25°C for 24 hours, impedance measurements were performed before cyclic voltammetry and constant current charge-discharge measurements. The obtained data were fitted using the analysis software ZView2 to estimate the diffusion resistance. Fig.33A The equivalent circuit model is shown.
[0230] (Comparative Example 4-1) A capacitor was produced in the same manner as in Example 4-1 except that the active material was changed to the carbon material of Comparative Example 1, and the diffusion resistance was estimated.
[0231] FIG. 33A to FIG. 33C is an equivalent circuit model for calculating the diffusion resistance in Example 4-1 and Comparative Example 4-1 ( Fig.33A ), Nyquist diagram of Example 4-1 ( Fig.33B ), Nyquist plot of Comparative Example 4-1 ( Fig.33C ).Depend on Fig.33B , Fig.33C The diffusion resistance W1 was calculated from the fitting curve of the Nyquist plot. The diffusion resistances of Example 4-1 and Comparative Example 4-1 were 17.48Ω and 22.93Ω, respectively. Therefore, in the capacitor of Example 4-1, the diffusion resistance was reduced by using the porous carbon material of Example 2.
[0232] The rate characteristics of the capacitors of Example 4-1 and Comparative Example 4-1 were evaluated by measuring the change in capacitance when the current value was increased. Fig.34 It is a graph showing the rate characteristics of Example 4-1 and Comparative Example 4-1.
[0233] according to Fig.34 It was confirmed that in Example 4-1, the capacitance decrease accompanying the increase in current value was suppressed compared with Comparative Example 4-1. The rate characteristics depend on the diffusion resistance and the DC resistance. In Example 4-1, it is believed that the reduction in diffusion resistance contributes greatly to the improvement of the rate characteristics. Therefore, it can be seen that the rate characteristics can be improved by flexibly applying the porous carbon material of Example 2 to EDLC.
[0234] In addition, in Example 4-1, since the primary particles were plate-like in shape, the inter-particle resistance of the active material that affects the DC resistance was also reduced, which is considered to lead to an improvement in the rate characteristics.
[0235] (Example 4-2) The capacitor was fabricated and the diffusion resistance was measured in the same manner as in Example 4-1, except that the equivalent circuit model used in estimating the diffusion resistance was changed to the model shown in FIG. 35( a ).
[0236] (Comparative Example 4-2) The capacitor was fabricated and the diffusion resistance was measured in the same manner as in Comparative Example 4-1, except that the equivalent circuit model used in estimating the diffusion resistance was changed to the model shown in FIG. 35( a ).
[0237] FIG. 35A to FIG. 35C is an equivalent circuit model for calculating the diffusion resistance in Example 4-2 and Comparative Example 4-2 ( Fig.35A ), Nyquist diagram of Example 4-2 ( Fig.35B ), Nyquist plot of Comparative Example 4-2 ( Fig.35C ).right Fig.35B , Fig.35C When the Nyquist plot of the embodiment 4-2 and the comparative example 4-2 were fitted, the diffusion resistances were 8.454Ω and 22.96Ω, respectively. Therefore, it was confirmed that even Fig.35A In the equivalent circuit model shown, by using the porous carbon material of Example 2, the diffusion resistance is also reduced.
[0238] The capacitor electrode using the porous carbon material of this embodiment has low diffusion resistance. In addition to electronic conductivity, the capacitor electrode also has multiple voids in the material derived from the porous structure of the material, and the large specific surface area can provide a reaction area with a high ion adsorption amount. At the same time, the electrolyte is immersed in the voids, and the adsorption, desorption and supply of lithium ions are rapidly performed during the electrochemical reaction. In addition, the high-speed electronic conduction brought by the graphene structure can achieve high-speed reactivity as a capacitor electrode.
[0239] Next, examples of the power storage device according to the present embodiment, specifically, output characteristic evaluation of a coin-type lithium ion battery as an example of the power storage device will be described.
[0240] <Evaluation of high output characteristics based on test battery>
[0241] (Example 5) <Preparation of test battery> 95 wt% of the NCM positive electrode material (Li 1.01 Ni 0.33 Co 0.33 Mn 0.33O2) powder, 2 wt% of the porous carbon material of Example 1 as a conductive aid, and 3 wt% of PVdF are stirred and mixed evenly with N-methyl-pyrrolidone (NMP) as a solvent to make a positive electrode paste. After coating it on an Al collector with a thickness of 15 μm, it is dried at 110°C, then punched into Φ15mm, and pressed at 30kN to make a negative electrode. After the electrode is vacuum dried at 120°C, in an argon atmosphere glove box, the electrolyte uses 1M LiPF6 solution (a 1:1 mixed solvent of ethylene carbonate (EC): diethyl carbonate (DEC)) and a polypropylene separator to make a 2032-size coin-type test battery with a metal Li counter electrode.
[0242] <Test Battery Evaluation> For each test battery, a constant current of 1mA (equivalent to 0.2C) is applied to 4.2V, and a constant voltage charge is performed after reaching 4.2V, which continues until 0.05mA (0.05C). Then, a constant current of 1mA is discharged to 3V. The discharge capacitance and average voltage at this time are obtained. Next, the same test battery is used, and a constant current of 1mA (equivalent to 0.2C) is applied to 4.2V, and a constant voltage charge is performed after reaching 4.2V, which continues until 0.05mA (0.05C) is reached. Then, a constant current of 30mA (equivalent to 5C) is discharged to 3V. Fig.37 A discharge curve showing different currents during discharge.
[0243] The discharge capacity and average voltage in the above evaluation test were calculated. Then, the 5C maintenance rate (5C capacity ÷ 0.2C capacity) and the average voltage drop (0.2C average voltage - 5C average voltage) were calculated.
[0244] (Comparative Example 5-1) A test cell was prepared under the same conditions as in Example 5 except that the carbon material of Comparative Example 1 was used as the conductive additive instead of the porous carbon material of Example 1. The test cell was then evaluated in the same manner as in Example 5.
[0245] (Comparative Example 5-2) A test cell was prepared under the same conditions as in Example 5 except that the carbon material of Comparative Example 2 was used as the conductive auxiliary agent instead of the porous carbon material of Example 1. The test cell was then evaluated in the same manner as in Example 5.
[0246] (Comparative Example 5-3) A test cell was prepared under the same conditions as in Example 5-1 except that the carbon material of Comparative Example 3 was used as the conductive auxiliary agent instead of the porous carbon material of Example 1. The test cell was then evaluated in the same manner as in Example 5.
[0247] (Comparative Example 5-4) A test cell was prepared under the same conditions as in Example 5-1 except that acetylene black (manufactured by Denki Kagaku Kogyo Co., Ltd., trade name: DENKA BLACK) was used as the conductive additive instead of the porous carbon material of Example 1. The test cell was then evaluated in the same manner as in Example 5.
[0248] The results are shown in Table 4.
[0249] [Table 4]
[0250] The porous carbon material of this embodiment fully functions as a conductive auxiliary agent for the positive electrode, and shows a high capacitance retention rate and a high discharge voltage even at high current, showing that the high output characteristics are improved. According to the porous carbon material of this embodiment, in addition to electronic conductivity, there are multiple voids in the material derived from the porous structure of the material, and the electrolyte is impregnated in the voids, which can quickly supply lithium ions during the battery reaction, and then through the high-speed electronic conduction brought by the graphene structure, the high-speed reactivity of the active material can be achieved.
[0251] The above-mentioned effect is not limited to positive electrode materials, and can also be preferably applied to negative electrode materials. In addition to the usual graphite negative electrode, Li alloy negative electrode materials such as Si can also achieve the effects of electronic conduction and ion conduction. Therefore, when the positive electrode and the negative electrode are used separately and / or the positive and negative electrodes are used, the output characteristics of the battery can be improved. Description of Reference Numerals
[0252] 10A, 10B: primary particles; 11: first wall portion; 12: second wall portion; 20: porous casting mold; 30: Molding; 35: Carbon layer; 100A: porous carbon material (GMS); 100B: porous carbon material (CMS); P: pores; Da: pore diameter (of porous carbon materials); D: average skeleton thickness (of porous castings); Db: pore diameter (of porous casting mold); G: gap; 200: power storage device (lithium-ion battery); 211: Exterior parts; 212: positive electrode; 213: Exterior parts; 214: negative electrode; 215: diaphragm; 217: Sealing gasket; 218: Spring; 219: Spacer.
Claims
1. A porous carbon material having a graphene skeleton, wherein: A plurality of pores are provided inside the primary particles constituting the porous carbon material. The particle diameter of the primary particles is 300 nm or more and 30 μm or less.
2. The porous carbon material according to claim 1, wherein The porous carbon material has a plate-like shape in which the ratio of the in-plane length of the primary particles to the thickness is 3 times or more.
3. The porous carbon material according to claim 1 or 2, wherein: The primary particles are plate-like in shape, The porous carbon material includes a first wall portion that mainly constitutes a plate-shaped main surface, and a second wall portion that constitutes a part of a partition wall inside the primary particle.
4. The porous carbon material according to claim 1 or 2, wherein: The diffusion resistance of a capacitor obtained by using the porous carbon material is 20Ω or less.
5. The porous carbon material according to claim 1 or 2, wherein The porous carbon material has a pore diameter of 2 nm or more and 50 nm or less.
6. A method for producing a porous carbon material, wherein: The method for producing the porous carbon material comprises: a coating step in which a carbon layer is coated on a porous mold having a primary particle size of 300 nm or more and 30 μm or less to obtain a molded product; as well as A separation step in which the porous mold is dissolved with an acid to separate the molded object from the porous mold.
7. The method for producing a porous carbon material according to claim 6, wherein: Prior to the coating step, a heat treatment step of heat-treating the porous mold is further included.
8. The method for producing a porous carbon material according to claim 6 or 7, wherein: The porous casting mold is composed of particles comprising an oxide of an alkaline earth metal.
9. The method for producing a porous carbon material according to claim 8, wherein: The alkaline earth metal oxide is magnesium oxide.
10. The method for producing a porous carbon material according to claim 8, wherein: In the separation step, the porous mold is dissolved with an acid that does not contain hydrofluoric acid.
11. The method for producing a porous carbon material according to claim 6, wherein: After the separation step, there is further included a stabilization step of heat-treating the molded product separated from the porous mold in the separation step.
12. The method for producing a porous carbon material according to claim 6, wherein: The average skeleton thickness of the porous casting mold is 70 nm or less. 13 . A capacitor electrode comprising an electrode using the porous carbon material according to claim 1 . 14 . A negative electrode for an electricity storage device, comprising the porous carbon material according to claim 1 as a conductive auxiliary agent. 15 . A positive electrode for an electricity storage device, comprising the porous carbon material according to claim 1 as a conductive auxiliary agent. 16 . An electricity storage device comprising a positive electrode and / or a negative electrode comprising the porous carbon material according to claim 1 as a conductive auxiliary agent.
Citation Information
Patent Citations
Lighting apparatus for vehicle
JP1989060448A
Porous carbon material production method
JP2021084819A